Enhancing Simulation Learning Through Collaborative Debriefing Papers - Martinez, Kelly (Nurse Educator, 2026)
Keywords: dept.nur

Redesigning ecosystems for all children to enhance health and well-being: An American Academy of Nursing consensus paper - Maughan, Erin D.; Meiers, Sonja J.; Breitenstein, Susan M.; Coffey, Jean S.; Cowen, Kay J.; Danford, Cynthia A.; Dodd, Catherine; King, Simmy; O'Malley, Donna M.; Resha, Cheryl-Ann; Sullivan, Mary C.; Lee, Susan K. (Nursing Outlook, 2026)
Although there have been many changes to community and family structure, and advances in scientific understanding of children's health and wellbeing, there has been little difference in how healthcare is delivered to children. The focus is often a deficit approach to acute situations. Halfon's Life Course Health Development Theory (LCHDT) focuses on a holistic approach to health and well-being. In the LCHDT, one's health is impacted by specific contexts during childhood that have a lasting impact. Key areas of family, community, schools, environment, and healthcare systems impart positive and negative experiences that affect children's health. Using the LCHDT as a guide, this consensus paper explores these five areas in the context of nursing practice roles and policy implications. With this approach, nurses lead and partner to build positive ecosystems for children and inform key policy actions to ensure change is a reality. © 2026 Elsevier Inc.
Keywords: Adolescents; Children; Ecosystems; Healthcare policy; Nursing care; dept.nur

Making arterial blood gas compensation memorable using a “buddy system” analogy - Diaz-Herring, Rosa (Nurse Educator, 2026)
Keywords: Analogy; Arterial blood; Blood gas analysis; Blood pressure; Compensation (psychology); dept.nur

Transforming clinical faculty preparation: A multistudent, multipatient simulation for nurse educator students - Kulacz, Regina; Lamberti, Amanda; Forte, Pamela; Lacey, Kimberly (Clinical Simulation in Nursing, 2026)
Keywords: Clinical Practice; Clinical faculty; Clinical judgment; Faculty development; Graduate students; Multipatient; Multistudent; Nurse education; Nurse educator; Nursing; Postgraduate; Role transition; Simulation; Student nurse; dept.nur

Restorative Masculine Integration Theory - Angelucci, Todd; Gallegos, Julian (American Journal of Men s Health, 2025)
The Restorative Masculine Integration Theory (RMIT) introduces a strengths-based, systems-oriented framework for promoting healthy masculinity through healing, leadership, and relational engagement. Developed in response to the adverse effects of masculine suppression, such as emotional disengagement, burnout, and polarity collapse, RMIT outlines a five-phase Cycle of Masculine Restoration: reclaimed masculinity, emotional safety and trust, grounded leadership, rebalanced gender polarity, and healing with cultural renewal. These stages are underpinned by core concepts including psychological safety, peer mentorship, emotional literacy, and authentic masculinity. Drawing from interdisciplinary foundations in gender studies, emotional intelligence, trauma-informed practice, polarity theory, and servant leadership, RMIT offers an adaptable framework for use across clinical, educational, organizational, and policy settings. Its alignment with the MANifest Health Theory further strengthens its applicability in men's health promotion. This manuscript elaborates the theory's conceptual development, visual model, and practical implications, while identifying future directions for empirical validation and inclusive application. RMIT advances a timely and restorative model for transforming masculine identity into a source of individual and collective resilience.
Keywords: Conceptual framework; Conceptual model; Culture theory; Empirical research; Gender identity; Grounded theory; Identity (music); Masculinity; PsycINFO; dept.nur; emotional literacy; masculinity; men’s health; peer mentorship; polarity; psychological safety; theory development; trauma-informed care

Virtual Faculty Development Program for Doctoral Advising - Penny, Frances (Nurse Educator, 2025)
Keywords: Academic advising; Career development; Faculty development; MEDLINE; Professional development; Virtual patient; dept.nur

Factors Contributing to Increased Mental Health Symptoms and Suicidality Among Sexual and Gender Minority Youth: A Scoping Review of Quantitative Research - Lopes, Daniela (Journal of Psychosocial Nursing and Mental Health Services, 2025)
Keywords: Anxiety; Clinical psychology; Depression (economics); Medicine; Mental health; Poison control; Psychiatry; Psychological intervention; Psychology; Psychosocial; Sexual minority; Sexual orientation; Suicidal ideation; Suicide prevention; dept.nur

Generational Differences in Nursing Students' Perceptions of Faculty Caring Behaviors and Presence in Online Registered Nurse to Bachelor of Science in Nursing Programs. - Macario, Kimberly Cardaci (International Journal for Human Caring, 2025)
Abstract: The purpose of this study was to explore how students of different generations perceived presence and caring behaviors by faculty in online Registered Nurse to Bachelor of Science in Nursing programs. Results showed that millennials reported statistically significant higher perceptions of social presence when compared with nonmillennials. Although generation was not a predictor of caring, all presence subscales were positively and significantly correlated with the total caring score. Teaching presence was a significant predictor of students' perceptions of caring in online courses.
Place: New York, New York
Keywords: Adult; Adult: 19-44 years; Age Factors; Caring Evaluation; Colleges and Universities; Conceptual Framework; Convenience Sample; Correlational Studies; Descriptive Research; Descriptive Statistics; Education; Non-Traditional; Education; Nursing; Baccalaureate; Educational Measurement; Exploratory Research; Faculty; Nursing; Faculty-Student Relations; Human; Intergenerational Relations; Learning Environment; Middle Age; Middle Aged: 45-64 years; Nursing Practice; Evidence-Based; Presence; Professional-Patient Relations; Program Evaluation; Quantitative Studies; Questionnaires; Registered Nurses Psychosocial Factors; Regression; Social Behavior Evaluation; Statistical Significance; Student Attitudes Evaluation; Students; Nursing Psychosocial Factors; Summated Rating Scaling; Teaching Methods; United States; dept.nur

Summer Nursing Symposium: An Immersive Educational Program Inspiring Underrepresented Minorities for College and a Career in Nursing - Knickerbocker, Joshua; Krol, Maria; Bartlett, Andrew; Borgognone, Kristen; Martinez, Kelly (Hispanic Health Care International, 2025)
Keywords: Medical education; Medicine; Nurse education; Nursing; Psychology; Underrepresented Minority; dept.nur; peer-reviewed

Teaching teamwork and collaboration: A task-centered clinical design - Morrill, Deborah (Nurse education today, 2018)
Keywords: dept.nur

Become a journal reviewer: a vital component of lifelong learning - Resha, Cheryl (The Journal of School Nursing, 2024)
Keywords: dept.nur

Collaborating to prepare students for perioperative nursing - Lacey, Kimberly; Forte, Pamela; Tammaro, Marie (Nurse Educator, 2024)
An abstract is unavailable.
Keywords: dept.nur; peer-reviewed

Use of student-created simulations to assess competency - Prendergast, Krista M.; Morrill, Deborah (Nurse Educator, 2024)
An abstract is unavailable.
Keywords: dept.nur; peer-reviewed

Use of an Affective Teaching Intervention to Impact Connections Between Academic and Professional Integrity - Morrill, Deborah (Southern Connecticut State University, 2021)
Dishonesty and misconduct of nursing students during their education is a continuing concern, especially as it relates to expected professional behaviors. This quasi experimental pre-and post-interventional study explored the impact of an affective learning module on developing beliefs and perceptions of ethicality of academic and professional misconduct of students in a BSN program. A modified version of McCrink’s (2008) tool, entitled “Nursing Student Experiences and Perceptions of Academic and Professional Conduct Survey” measured these constructs. The affective learning module, based on Rest’s theory of moral development, and Krathwohl’s affective taxonomy, actively engaged students in ethical decision-making with connections to professional practice through discussion, case review and reflection. The pretest data (N=65) analysis using Mann Whitney U, indicated differences in mean rank related to enrollment status, healthcare work experience and gender and beliefs, and perceptions of academic and professional misconduct. A comparative analysis (N=16) of pre and posttest data was limited due to required changes related to the COVID-19 pandemic. Changes in pre and posttest data suggest the need to replicate and continue research in the area of intentional affective teaching of ethicality and professional values.
Keywords: Affective domain; Affective taxonomy; Dishonesty; Integrity; Misconduct; Value development; dept.nur

An Innovative Academic/Practice Partnership to Support Nursing Workforce Needs and Student Clinical Education - Hahn, Judith; Resha, Cheryl-Ann; Beauvais, Audrey; Beckman, Beth; Forte, Pamela; Rebeschi, Lisa M.; Snyder, Marianne (JONA: The Journal of Nursing Administration, 2023)
Innovation is needed to solve nursing workforce issues during times of crisis. A collaborative effort between a hospital system and several universities resulted in the Bridge to Professional Practice Program that was implemented during a period of high patient volume and nursing student downtime. The program provided support for staffing needs and clinical hours to promote readiness for practice for students. The program evaluation outcomes and recommendations for improvement are addressed.
Keywords: dept.nur; peer-reviewed

Preface - Logan, Isabel; Green, Cheryl (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Keywords: dept.nur; dept.swk

Use of a supplemental feeding tube device and breastfeeding at 4 weeks - Penny, F.; Brownell, E.A.; Judge, M.; Marshall-Crim, M.; Cartagena, D.; McGrath, J.M. (MCN The American Journal of Maternal/Child Nursing, 2023)
Background:Mothers having difficulty breastfeeding their infants may use alternative supportive feeding methods. Although a supplemental feeding tube device is commonly used, efficacy for supporting sustained breastfeeding remains unknown.Purpose:To describe supplemental feeding tube device use by breastfeeding mothers as an alternative feeding method through exploration of associations between supplemental feeding tube device use and continued breastfeeding at 4 weeks of infant's age.Method:Forty mothers participated. They were interviewed during the birth hospitalization and at 4 weeks postpartum. Questions addressed use of supplemental feeding tube devices, breastfeeding issues, and continued breastfeeding relationships. We examined the relationship between LATCH scores at 2 to 3 days of life.Results:Breastfeeding mothers who chose to supplement with bottle-feeding instead of use of a supplemental feeding tube device were 30% less likely to continue breastfeeding at a medium/high/exclusive level.Conclusion:Use of the supplemental feeding tube device may help avoid the potentially detrimental effect of bottle-feeding on continued breastfeeding. © 2023 Lippincott Williams and Wilkins. All rights reserved.
Keywords: Baby-friendly hospital initiative; Bottle-feeding; Breast feeding; Breastfeeding exclusive; Exclusive breastfeeding; Human milk; Lactation; dept.nur; peer-reviewed

Unfolding health assessment case studies for the student nurse - Maynard, Kristi; Adimando, Andrea (Sigma Theta Tau International, 2020)
This book was designed with student nurses in mind. It is intended to serve as a tool to provide practice, enhance learning, and increase the propensity for retention and application of basic concepts of health and physical assessment. The book can be used by early-career nursing students who have just begun to cover its concepts as well as by pre-licensure exam students who may benefit from reiteration and reinforcement of concepts learned early on in nursing school and from practicing applying these concepts to more complex scenarios.Divided into 13 chapters, all of which are geared toward a particular subject matter. Chapters 1 and 2 introduce the concept of an unfolding case study and the nursing process. Chapter 3 provides an in-depth guide to answering NCLEX-style questions. There are several NCLEX-style questions broken down and analyzed within this chapter and several practice questions for your benefit. The remainder of the chapters are subject-based and cover assessment of the major body systems in a systematic and learner-friendly way. Readers will notice that while each chapter covers different content matter, the chapters are structured in similar ways so the reader can begin to develop a feel for and familiarity with an unfolding case study analysis.Goals for the book are:*Increased comfort level and confidence in analyzing patient scenarios in regards to basic health assessment *A more in-depth knowledge of basic health assessment concepts *Ample chances to practice applying concepts learned in your health assessment course to solidify the information you have learned*Increased confidence in answering NCLEX-style questions *Increased knowledge, skill levels, and confidence in assessing and managing patients with a variety of healthcare needsThe chapters of the book do not have to be completed in any particular order, as they are each individualized to certain subject matter categories. The authors recommend you use these unfolding case studies as a means of evaluating the ability to think critically and apply the concepts learned in health assessment classes to realistic patient scenarios. The book can be used as a study tool during health assessment classes, a health assessment refresher tool during other classes, and an NCLEX study tool after finishing nursing school.
Keywords: dept.nur

Stabilization approaches that empower clients through mental health crises - Logan, Isabel; Green, Cheryl A. (IGI Global, 2023)
Mental health practitioners often overlook initial stabilization strategies and interventions when providing evidence-informed approaches in order to get to the so-called “important” or “interesting” part of treatment. For many mental health practitioners, the “important” or “interesting” component...
Publication Title: https://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-7998-8228-2
Keywords: dept.nur; dept.swk

Grow through what you go through - Ortiz, Chelsea L. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
Being a millennial person-of-color in the twenty-first century is exhaustive in itself—adding the vulnerabilities of a global pandemic magnified that undertaking. As women, we bear the responsibilities of balancing our professional life with our family life; our role as a partner or friend with our role as an individual being; and our mental health with our social health. “Grow Through What You Go Through” explores the value of saying “Yes, I can do this too” when COVID-19 gave many a reason to say, “I’ve had enough.” Between being a supportive partner and family member to many who experienced financial and educational setbacks and being an important part of preparing the next set of future nurses to lead and excel during a global pandemic, COVID-19 enlightened my perspective on who I was at the start of COVID-19 and the person I would turn out to be by the end of it.
Keywords: COVID-19; Coping; Resilience; dept.nur

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
1 citations (Crossref) [2023-10-31]
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

[Chaos Theory and Its Application in Nursing Science] - Vicenzi, Angela (1995)
Keywords: dept.nur; faculty_collection; sabbatical_report

Contemporary Legal Issues Affecting Professional in Human Service Fields. - Killion, Susan (1992)
Keywords: dept.nur; faculty_collection

Professional Nurse Traineeship. - Beatty, Ellen (1988)
Keywords: dept.nur; faculty_collection; sabbatical_report

Community Health Nursing. - Milone-Nuzzo, Paula (1988)
Keywords: dept.nur; faculty_collection; sabbatical_report

Clinical Case Studies for the Family Nurse Practitioner - Neal-Boylan, Leslie (Wiley-Blackwell, 2011)
Keywords: Case studies; Case studies; Nurse practitioners; Family nursing; dept.nur; faculty_collection

Clinical Case Studies in Home Health Care - Neal-Boylan, Leslie (Wiley-Blackwell, 2011)
Keywords: Case studies; Home care services; dept.nur

Legal Resource for School Health Services - Resha, Cheryl A.; Taliaferro, Vicki (SchoolNurse.com, 2017)
A reference regarding legal issues impacting school health. The book provides information on over 50 topics that school health services programs and school nurses encounter, addresses legal implications and presents legal resources and references that can be applied to practice and policy development. - Cover
Keywords: Law and legislation; School nursing; United States; dept.nur; faculty_collection

School Nurse Resource Manual: A Guide to Practice - Taliaferro, Vicki; Resha, Cheryl A. (School Health Alert, 2017)
School nurses' work focuses directly on three areas: health services, health education, and the school environment. Their services require diverse knowledge including, but not limited to, pediatric/adolescent health, infectious diseases, mental health, chronic diseases, and emergency care. They can influence health and safety aspects of schools and can provide leadership to a district's or campus' coordinated school health program that in addition to health services, health education, and the school environment addresses mental health and social services, nutrition services, physical activity, family and community involvement, and/or staff health promotion. This work is written for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidence-based policies and procedures for safe student care.
Keywords: Handbooks; manuals; etc; School Nursing; School nursing; dept.nur; faculty_collection

Essentials of nursing law and ethics - Westrick, Susan J. (Jones & Bartlett Learning, 2014)
Keywords: Law and legislation; Nursing ethics; Nursing; United States; dept.nur; faculty_collection

Sabbatical leave report: sabbatical Fall 2012 / submitted by: Susan J. Westrick, Professor, Department of Nursing. - Westrick, Susan J. (2012)
This sabbatical project involved re-writing as the sole author a previously co-authored textbook, Essentials of Nursing Law and Ethics (2009), devoted to traditional and contemporary legal and ethical concerns for nursing students and practicing nurses.
Keywords: dept.nur; faculty_collection; sabbatical_report

Essentials of Nursing Law and Ethics - Westrick, Susan J. (Jones and Bartlett Publishers, 2009)
Keywords: Law and legislation; Nursing ethics; Nursing; United States; dept.nur; faculty_collection

Evidence-Based Nursing Guide to Legal & Professional Issues. - Westrick, Susan J.; Lippincott Williams & Wilkins (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
Keywords: Law and legislation; Nursing; United States; dept.nur; faculty_collection

The Pediatric Nurse's Survival Guide - Rebeschi, Lisa M.; Brown, Mary H. (Thomson Delmar Learning, 2007)
Keywords: Handbooks; manuals; etc; Pediatric nursing; dept.nur; faculty_collection

Legal and Ethical Issues - Westrick, Susan J.; Dempski, Katherine (Jones and Bartlett, 2006)
Keywords: Law and legislation; Nursing ethics; Nursing; dept.nur; faculty_collection

Pathophysiology - Crutchlow, Eileen M. (Slack, 2002)
Keywords: Physiology; Pathological; Nursing; dept.nur; faculty_collection

The Pediatric Nurse's Survival Guide - Rebeschi, Lisa M. (Delmar, 2002)
Keywords: Handbooks; manuals; etc; Pediatric nursing; dept.nur; faculty_collection

Legal and Ethical Issues - Westrick, Susan J.; Dempski, Katherine (SLACK Inc., 2000)
Keywords: Law and legislation; Nursing ethics; Nursing; dept.nur; faculty_collection

A Nursing Home and Its Organizational Climate: An Ethnography - Farmer, Bonnie Cashin (Auburn House, 1996)
Keywords: Case studies; Case studies; Corporate culture; Meadows of Madison (Nursing home); Nursing homes; Sociological aspects; dept.nur; faculty_collection

The Pediatric Survival Guide - Rebeschi, Lisa M.; Brown, Mary L. (Skidmore-Roth Pub., 1996)
Keywords: dept.nur; faculty_collection

Workplace Health Promotion in a Sample of New York State Small Businesses: A Description of Current Programs and Associated Organizational Factors - Vicenzi, Angela E. (University Microfilms International, 1984)
Keywords: Health promotion; dept.nur; faculty_collection

Integration of the Registered Nurse Care Coordinator Role in a Federally Qualified Health Center - Alicea-Planas, Jessica; Burger, Susan (The Journal of Ambulatory Care Management, 2023)
The purpose of this 1-group, retrospective case study was to analyze the expanded role of registered nurse care coordination (RNCC) on health outcomes in a primary care setting in its real-life context. The convenience sample consisted of 244 adults diagnosed with uncontrolled diabetes mellitus and/or hypertension. Secondary data entered into the electronic health record by the health care team during patient visits pre- and post-implementation of the RNCC program were analyzed. Clinical findings suggest that RNCC may provide a valuable service. Additionally, financial analysis demonstrated that the cost of the RNCC position was both self-sustaining and revenue producing.
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

A telemedicine standardized patient experience: enhancing the virtual classroom and preparing for alternative modalities of care - Maynard, Kristi; Knickerbocker, Joshua (Nursing Education Perspectives, 2023)
This pilot study explored the use of standardized patients in the virtual classroom in efforts to increase family nurse practitioner preparedness to engage in telemedicine care delivery. Using a mixed-methods approach, we determined this innovation significantly increased students' confidence in their ability to perform a telemedicine visit while also improving their satisfaction with the virtual classroom.
1 citations (Crossref) [2023-10-31]
Keywords: Delivery of Health Care; Humans; Personal Satisfaction; Pilot Projects; Students; Telemedicine; dept.nur; peer-reviewed

Diabetes Distal Peripheral Neuropathy: Subtypes and Diagnostic and Screening Technologies - Newlin Lew, Kelley; Arnold, Tracey; Cantelmo, Catherine; Jacque, Francky; Posada-Quintero, Hugo; Luthra, Pooja; Chon, Ki H. (Journal of Diabetes Science and Technology, 2022)
Diabetes distal symmetrical peripheral neuropathy (DSPN) is the most prevalent form of neuropathy in industrialized countries, substantially increasing risk for morbidity and pre-mature mortality. DSPN may manifest with small-fiber disease, large-fiber disease, or a combination of both. This review summarizes: (1) DSPN subtypes (small- and large-fiber disease) with attention to clinical signs and patient symptoms; and (2) technological diagnosis and screening for large- and small-fiber disease with inclusion of a comprehensive literature review of published studies from 2015-present (N = 66). Review findings, informed by the most up-to-date research, advance critical understanding of DSPN large- and small-fiber screening technologies, including those designed for point-of-care use in primary care and endocrinology practices.
3 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

Moral distress in emergency and critical care nurses: A metaethnography - Arnold, Tracey C (Nursing Ethics, 2020)
Background:Moral distress has detrimental effects on nurses which impacts the entire healthcare cycle. Described as a crescendo effect, resolved situations of moral distress leave residue on the nurse with three potential outcomes: moral numbing, conscious objection to the situation, and burnout.Objective:This metaethnography strives to achieve a fuller understanding of moral distress by interpreting the body of qualitative work of moral distress in emergency and critical care nurses.Method:This study used the Noblit and Hare?s approach of interpretative synthesis. Ten studies met the criteria and were used in this synthesis.Ethical considerations:Ethical issues were minimal since no human subjects were involved. Ethical requirements were respected in all study phases.Results:The synthesis of qualitative research on moral distress resulted in one central theme, ?the battle within,? and five subthemes.Conclusions:The unique nature of this nursing specialty resulted in a lasting inner conflict for nurses that is consistent with the previously described crescendo effect. The effects are complex and long lasting and may potentially affect the nurses? future patient care.
17 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

An evolutionary concept analysis of secondary traumatic stress in nurses - Arnold, Tracey (Nursing Forum, 2020)
Purpose The purpose of this article is to provide conceptual clarification of secondary traumatic stress (STS) in nurses. Background As an empathetic helping profession, nurses are at increased risk for STS. Interchangeable usage of related terms among multidisciplinary literature has resulted in lack of conceptual clarity resulting in conflation of terms. Conceptual clarity is necessary for a foundation for further research on treatment. Methods Rodgers' evolutionary model of concept analysis. Results Nurses are predisposed to STS due to exposure, empathy, bonding, and personal factors. Essential attributes were found to be posttraumatic stress disorder-like symptoms, biological symptoms, social symptoms, and psychological symptoms. Resultant consequences included an altered worldview, interpersonal difficulties, and decreased occupational commitment. Conclusion This concept analysis, the first focusing on STS, provides conceptual clarity and a concept map of STS within the nursing population.
17 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/nuf.12409
Keywords: Rodgers' evolutionary model; concept analysis; concept map; dept.nur; peer-reviewed; secondary traumatic stress

Humanizing substance abuse: a theory-based educational intervention for undergraduate nursing students - Roncallo, Hannah R.; Aronson, Barbara (Journal of Addictions Nursing, 2023)
Background Healthcare providers, as well as healthcare students, have been found to harbor negative attitudes toward individuals with substance abuse disorders, impacting the care they give and subsequently creating poor patient outcomes. Purpose This study seeks to determine the effectiveness of an educational intervention, grounded in theory, toward changing nursing student attitudes regarding patients with a substance abuse disorder. Methods Nursing students participated in a teaching intervention, developed using the experiential learning theory, that utilizes modalities for each kind of learner aimed at reducing bias toward this population. The Medical Condition Regard Scale was used pre/post intervention to determine regard toward patients with the diagnosis of substance abuse. Results Student nurses maintained the least favorable attitudes toward individuals who abuse substances in comparison with patients with the diagnoses of pneumonia or gastroesophageal reflux disease; there were significant differences in attitudes toward patients who abused substances before and after participation in the educational intervention, with postparticipation attitudes being significantly more positive than attitudes before participation. Students found the educational intervention and debriefing highly satisfactory. Implications This educational intervention can provide a cost-effective, easy-to-replicate, time-efficient learning activity that could be added to undergraduate nursing curriculum.
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

Differences in Neonatal Outcomes Among Premature Infants Exposed to Mother's Own Milk Versus Donor Human Milk - Cartagena, Diana; Penny, Frances; McGrath, Jacqueline M.; Reyna, Barbara; Parker, Leslie A.; McInnis, Joleen (Advances in Neonatal Care: Official Journal of the National Association of Neonatal Nurses, 2022)
BACKGROUND: Growing evidence supports the superior benefits of exposure to mother's own milk (MOM) in reducing prematurity-related comorbidities. Neonatal exposure to donor human Milk (DHM) is a suitable alternative when MOM is insufficient or unavailable. However, the same protective composition and bioactivity in MOM are not present in DHM. Additional evidence is needed to justify and inform evidence-based practices increasing MOM provision while optimizing adequate use of DHM for premature infants. PURPOSE: A systematic review of the literature was conducted to determine differences in neonatal outcomes among premature infants exposed to predominately MOM versus DHM. METHODS/SEARCH STRATEGY: Databases including PubMed, CINAHL and Cochrane were searched (2020-2021) using the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analysis) guidelines. Evidence was classified using the John Hopkins evidence-based practice levels and quality of evidence. RESULTS: Eleven studies met inclusion criteria. Studied neonatal outcomes included ( a ) growth parameters (n = 8), ( b ) neonatal morbidities (n = 6), and ( c ) gut microbiome (n = 4). Overall, evidence suggests DHM exposure is beneficial but not equivalent to MOM feeding. Compared with DHM, greater doses of MOM are ideal to enhance protection primarily related to infant growth, as well as gut microbiome diversity and richness. IMPLICATIONS FOR PRACTICE: Standardized and evidence-based practices are needed to clearly delineate optimal use of DHM without undermining maternal and neonatal staff efforts to support and promote provision of MOM. IMPLICATIONS FOR RESEARCH: Additional evidence from high-quality studies should further examine differences in neonatal outcomes among infants exposed to predominately MOM or DHM in settings using standardized and evidence-based feeding practices.
2 citations (Crossref) [2023-10-31]
Keywords: Breast Feeding; Female; Humans; Infant; Infant; Newborn; Infant; Premature; Infant; Very Low Birth Weight; Intensive Care Units; Neonatal; Milk; Human; Mothers; dept.nur; peer-reviewed

Fostering Nursing Students' Moral Decision-Making Through Use of an Affective Learning Module - Morrill, Deborah; Westrick, Susan J. (Nurse Educator, 2022)
Background: The emphasis on disciplinary and preventive approaches to combating academic misconduct does little to foster student professional identity and core nursing value formation. Problem: There is a need for pedagogy designed to navigate moral decision-making within ambiguous areas of practice as nursing students integrate personal and professional values while becoming a nurse. Approach: Rest's theory of moral development offers a framework for constructing purposeful affective learning activities that operationalize moral sensitivity, judgment, motivation, and character, whereas Krathwohl's theory provides a means to identify affective learning objectives. Offering prelicensure nursing students an opportunity to discuss, reflect on, and consider actions and consequences associated with academic and practice-based situations forms the basis for this affective learning module that fosters connections between academic and professional behaviors of integrity. Conclusion: Rest's theoretical model provides a viable structured approach to moral development. Curriculum designed to engage moral decision-making offers an innovative approach to cultivating student integrity.
1 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

Interleukin-1 induces time-dependent potentiation in isolated rat islets: Possible involvement of phosphoinositide hydrolysis - Zawalich, W.S.; Dierolf, B.; Zawalich, K.C. (Endocrinology, 1989)
Prior exposure of isolated perifused rat islets to the monokine interleukin-1 (IL-1) amplifies their subsequent insulin secretory response to 10 mM glucose. This potentiating effect of the monokine is dose dependent, lasts for at least 45 min after IL-1 removal from the medium, and is not confined to glucose; IL-1 also potentiates the insulin secretory responses to tolbutamide and glyceraldehyde. IL-1 exposure of islets incubated with myo-[2â€ 3H]inositol to label their phosphoinositides (PI) results in an increase in [3H]inositol efflux, an event that persists long after removal of IL-1 from the medium. Direct measurements of labeled inositol phosphate accumulation substantiate the concept that this sustained [3H] inositol efflux response is the direct result of a sustained increase in PI hydrolysis. These results expand the list of compounds that induce time-dependent potentiation in islets to include IL-1. This action of the monokine, mediated at least in part by Pi-derived second messenger molecules, may contribute to its postulated effects on insulin and glucose homeostasis. © 1989 by The Endocrine Society.
Keywords: Animal; Hydrolysis; In Vitro; Inositol Phosphates; Insulin; Interleukin-1; Islets of Langerhans; Kinetics; Male; Phosphatidylinositols; Rats; Rats; Inbred Strains; Reference Values; Support; Non-U.S. Gov't; Time Factors; animal cell; controlled study; dept.nur; insulin; interleukin 1; male; nonhuman; pancreas islet; phosphatidylinositide; priority journal; radioisotope; rat; tolbutamide; ⚠️ Invalid DOI

The sundown syndrome: Will the specialized training of nurse's aides help elders with sundown syndrome? - Wallace, M. (Geriatric Nursing, 1994)
3 citations (Crossref) [2023-10-31]
Keywords: Aged; Humans; Nurses' Aides; Social Behavior Disorders; Time Factors; aged; article; dept.nur; human; nursing; nursing assistant; sociopathy; time

Nursing Diagnosis in Home Care: Audit Tool Development - Zink, M.R. (Journal of Community Health Nursing, 1994)
Little research has been done to document the value of using nursing diagnosis in home care and the impact that increased acuity levels have had in diagnostic selection. Nursing diagnosis documentation in home care was examined to see whether it had a relation to select client and visit pattern variables. This retrospective chart audit, which piloted a newly developed instrument called the Home Care Audit Tool, utilized a sample of 199 closed records of a large midwestem Visiting Nurse Association. The mean age of the client population was 76 years, with 64% female. There were 269 initial nursing diagnoses cited in the sample records, averaging 1.75 diagnoses per case. The number of recorded visits increased when select nursing diagnoses were cited together in a single case. © 1994, Taylor & Francis Group, LLC. All rights reserved.
5 citations (Crossref) [2023-10-31]
Keywords: Aged; Community Health Nursing; Female; Home Care Services; Human; Male; Models; Nursing; Nursing Audit; Nursing Diagnosis; Nursing Records; Pilot Projects; Reproducibility of Results; Retrospective Studies; Severity of Illness Index; article; community care; dept.nur; home care; medical assessment; nursing; nursing education

Nursing ethics committees —where are they? - Zink, M.R.; Titus, L. (Nursing Management, 1994)
When establishing Nursing Ethics Committees (NECs), statewide nursing organizations play an important role in developing and disseminating resources. The Connecticut Nurses Association Ethics and Human Rights Committee surveyed 85 healthcare facilities to identify active NECs. Representatives facilitated other committees by providing guidelines and assistance to those agencies developing NECs — the ultimate goal. © 1994 by Springhouse Corporation.
2 citations (Crossref) [2023-10-31]
Keywords: Bioethics and Professional Ethics; Clinical Approach/Source; Connecticut; Empirical Approach; Ethics Committees; Ethics Committees; Clinical; Ethics; Nursing; Human; Patient Advocacy; Questionnaires; Survey; United States; article; dept.nur; human; human rights; medical ethics; organization and management; professional standard; questionnaire; survey

Dual assignment: An alternative clinical teaching strategy - Fugate, T.; Rebeschi, L.M. (Nurse Educator, 1992)
Meeting students’ learning needs in acute care settings is challenging. The authors discuss dual assignment in the pediatric setting with beginning nursing students. © 1992 Lippincott-Raven Publishers.
1 citations (Crossref) [2023-10-31]
Keywords: Clinical Competence; Education; Nursing; Baccalaureate; Human; Pediatric Nursing; article; competence; dept.nur; education; human; methodology; nursing; nursing education; standard

Dual assignments: An effective clinical teaching strategy - Gotschall, L.A.; Thompson, C. (Nurse Educator, 1990)
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur

Caring for a young child in a body cast: Impact on the care giver - Newman, D.M.L.; Fawcett, J. (Orthopaedic Nursing, 1995)
Data from an open-ended questionnaire and the comments section of a structured questionnaire were combined and ana-lyzed to determine the challenges faced and alterations in usual daily activities required by mothers caring for a young child at home in a body cast. The sample consisted of 35 mothers who identified themselves as the primary care givers of a child in a body cast. The challenges of caring for a child in a body cast required major adjustments in almost every aspect of the mothers' lives, including household activities, social and community activities, child care activities, personal care activities, occupational activities, and educational activities. © 1995 National Association of Orthopaedic Nurses.
17 citations (Crossref) [2023-10-31]
Keywords: Adolescent; Adult; Caregivers; Casts; Surgical; Child; Preschool; Cost of Illness; Female; Hip Dislocation; Congenital; Home Nursing; Human; Infant; Infant; Newborn; Male; Mothers; Questionnaires; Support; Non-U.S. Gov't; adolescent; adult; article; caregiver; congenital hip dislocation; cost of illness; dept.nur; education; female; home care; human; infant; male; mother; newborn; nursing; plaster cast; preschool child; psychological aspect; questionnaire

Counselors’ conceptualizations of caring in the counseling relationship - Halstead, R.W.; Wagner, L.D.; Vivero, M.; Ferkol, W. (Counseling and Values, 2002)
Caring is a concept that has been studied in numerous helping professions but has yet to be researched from a counseling perspective. In this qualitative research study, 13 master’s-level counseling interns were interviewed to better understand their perceptions of caring in the counseling relationship. Results suggest that these interns perceive that supporting desired outcomes, a personal capacity for caring, maintaining therapeutic conditions, mutuality in the counseling relationship, and a dynamic flow of communication are important attributes of the counseling relationship when caring is present The findings suggest further research that explores the concept of caring in the counseling relationship may be warranted. © 2002 American Counseling Association.
2 citations (Crossref) [2023-10-31]
Keywords: dept.nur

Care of the Laparoscopic Nissen Fundoplication Patient - Aronson, B.S.; Yeakel, S.; Ferrer, M.; Caffrey, E.; Quaggin, C. (Gastroenterology Nursing, 2001)
Gastroesophageal reflux disease can usually be successfully managed with conservative medical treatment. Anti-reflux surgery is a safe alternative when treatment fails or patients desire a more definitive treatment option. Through a case study approach, this article describes the indications for surgery, the essentials of the authors’ multi-disciplinary approach to care and the components of a well-designed education plan for a patient undergoing laparoscopic Nissen fundoplication. Although most patients do well after surgery, diligent nursing care is required before and after surgery to prevent or manage complications and ensure patients have a rapid recovery and successful outcome. © 2001 Lippincott Williams & Wilkins, Inc.
3 citations (Crossref) [2023-10-31]
Keywords: Fundoplication; Gastroesophageal Reflux; Gastroscopy; Humans; Male; Middle Aged; Patient Care Team; Patient Discharge; Patient Education; Patient Selection; Perioperative Care; Treatment Outcome; case report; dept.nur; gastroesophageal reflux; gastroscopy; hospital discharge; human; male; methodology; middle aged; nursing; organization and management; patient care; patient education; patient selection; perioperative period; review; stomach fundoplication; treatment outcome

Pain in older adults - Wallace, M. (Annals of Long-Term Care, 2001)
Pain is a prevailing clinical problem among older adults resulting in systemic agitation and altered quality of life. Although the possibility remains that older adults experience and report less pain, the need exists to objectively evaluate pain in order to provide the most effective pain management. Several standardized tools are available to assess pain in older adults at baseline and at subsequent, frequent intervals. Following an objective assessment, pain may be managed with pharmacologic and nonpharmacologic methods.
Keywords: Alzheimer disease; acetylsalicylic acid; aged; amitriptyline; analgesic agent; anticonvulsive agent; carbamazepine; choline magnesium trisalicylate; clonazepam; codeine; corticosteroid; dementia; dept.nur; desipramine; dose response; doxepin; drug effect; drug formulation; drug indication; fentanyl; gabapentin; human; hydrocodone; hydromorphone; ibuprofen; imipramine; intravenous anesthetic agent; local anesthetic agent; morphine sulfate; naproxen; narcotic analgesic agent; nonsteroid antiinflammatory agent; nortriptyline; opiate; oxycodone; pain; pain assessment; paracetamol; prednisone; review; side effect; tricyclic antidepressant agent; unindexed drug; visual analog scale; ⛔ No DOI found

Moving forward together: The practice doctorate in nursing - O'Sullivan, A.L.; Carter, M.; Marion, L.; Pohl, J.M.; Werner, K.E. (Online Journal of Issues in Nursing, 2005)
Societal drivers, as well as trends in education and health care, are advancing the practice doctorate in nursing. For nurse practitioner preparation, the current resurgence of interest in the practice doctorate could precipitate change that mimics the evolution from post-basic certificate to Master's level education. The National Organization of Nurse Practitioner Faculties (NONPF) is a resource for the study of the practice doctorate relative to quality nurse practitioner education. This article will offer some insights into the movement toward the practice doctorate by describing, from the NP perspective, the societal impetus for change, the historical perspective of NP and doctoral education, the 4 Ws (why, what, where, and when) of the movement, and some of the myths and realities about the practice doctorate. © 2005 Online Journal of Issues in Nursing.
Keywords: NONPF; Nurse practitioner; Nursing education; Practice doctorate; cultural anthropology; demography; dept.nur; education program; evolution; health care; health care organization; health care quality; health care system; health practitioner; medical education; medical practice; nursing; review; ⛔ No DOI found

Carelink: Partners in a caring Model: A cardiac management program for home care - Shellman, J.; Lacey, K.; Clemmens, D. (Home Healthcare Nurse, 2008)
As a model of care, CARELINK promotes self-care and self-management of chronic illnesses for homebound older adults no longer eligible for skilled nursing services. A case-study method is used to highlight the key constructs and outcomes related to the model. The benefits of applying the CARELINK model as a cardiac management program for home care are discussed.
6 citations (Crossref) [2023-10-31]
Keywords: Aged; Chronic Disease; Education; Nursing; Empathy; Geriatric Nursing; Heart Diseases; Home Care Services; Humans; Male; Models; Nursing; Self Care; aged; article; chronic disease; dept.nur; education; empathy; geriatric nursing; heart disease; home care; human; male; methodology; model; nursing; nursing education; organization and management; self care

Abdominal pain - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Aching in legs - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Burning epigastric pain after meals - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Clinical case studies for the family nurse practitioner - Neal-Boylan, L. (wiley, 2011)
Clinical Case Studies for the Family Nurse Practitioner is a key resource for advanced practice nurses and graduate students seeking to test their skills in assessing, diagnosing, and managing cases in family and primary care. Composed of more than 70 cases ranging from common to unique, the book compiles years of experience from experts in the field. It is organized chronologically, presenting cases from neonatal to geriatric care in a standard approach built on the SOAP format. This includes differential diagnosis and a series of critical thinking questions ideal for self-assessment or classroom use. © 2011 by John Wiley & Sons, Inc.
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner Pages: 404 Publication Title: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Contraception - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Facial pain - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Fatigue and joint pain - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Headache - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Insomnia - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Introduction - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Keywords: dept.nur; ⛔ No DOI found

Knee pain - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Muscle tenderness - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Urinary frequency - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Vaginal itching - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Wrist pain and swelling - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Clinical Case Studies in Home Health Care - Neal-Boylan, L. (Wiley Blackwell, 2013)
Home health care is an important aspect of community health and a growing area of healthcare services. Clinical Case Studies in Home Health Care uses a case-based approach to provide home healthcare professionals, educators, and students with a useful tool for thoughtful, holistic care. The book begins with a thorough and accessible introduction to the principles of home health care, including a discussion of supporting theoretical frameworks and information on managing complexities, transitioning patients to home care, and preparation for the home visit. Subsequent sections are comprised entirely of case studies organized by body system. Though cases are diverse in content, each is presented in a consistent manner, incorporating relevant data about the patient and caregivers and the approach to patient care and promoting a logical approach to patient presentation. Cases also include helpful tips about reimbursement practices, cultural competence, community resources, and rehabilitation needs. © 2011 by John Wiley & Sons, Inc.
Journal Abbreviation: Clin. Case Stud. in Home Health Care Pages: 485 Publication Title: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Multiple Sclerosis - Neal-Boylan, L. (Clinical Case Studies in Home Health Care, 2013)
Journal Abbreviation: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Theoretical Frameworks That Support Home Care - Neal-Boylan, L. (Clinical Case Studies in Home Health Care, 2013)
Journal Abbreviation: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Case Studies in Gerontological Nursing for the Advanced Practice Nurse - Kazer, M.W.; Neal-Boylan, L. (Wiley Blackwell, 2011)
As the fastest growing population sector worldwide, older adults are seen in almost every care setting in which clinicians practice. Developed as a resource for advanced practice nurses in any setting, Case Studies in Gerontological Nursing for the Advanced Practice Nurse presents readers with a range of both typical and atypical cases from real clinical scenarios. The book is organized into six units covering cases related to ageism, common health challenges, health promotion, environments of care, cognitive and psychological issues, and issues relating to aging and independence. Each case follows a similar format including the patient's presentation, critical thinking questions, and a thorough discussion of the case resolution through which students and clinicians can enhance their clinical reasoning skills. Designed to promote geriatric clinical education through self-assessment or classroom use, Case Studies in Gerontological Nursing for the Advanced Practice Nurse is a key resource for all those dedicated to improving care for older adults. © 2012 by John Wiley & Sons, Inc. All rights reserved.
Journal Abbreviation: Case Stud. in Gerontol. Nurs. for the Adv. Pract. Nurse Pages: 398 Publication Title: Case Stud. in Gerontol. Nurs. for the Adv. Pract. Nurse
Keywords: dept.nur

Introduction - Case Studies in Gerontological Nursing for the Advanced Practice Nurse - Kazer, M.W.; Neal-Boylan, L. (Case Studies in Gerontological Nursing for the Advanced Practice Nurse, 2011)
Keywords: dept.nur

Are You in the Hospital Again? - Lacey, K.O. (Case Studies in Gerontological Nursing for the Advanced Practice Nurse, 2011)
Journal Abbreviation: Case Stud. in Gerontol. Nurs. for the Adv. Pract. Nurse
Keywords: dept.nur

NLN's simulation leaders give SIRC bibliography site a Makeover - Alfes, C.M.; Aronson, B.; Bethards, M.L.; Chesney, T.; De Luna, R.; Newton, R.; Weaver, A. (Nursing Education Perspectives, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: Databases; Bibliographic; Health Information Management; Humans; Internet; Models; Educational; Patient Simulation; Societies; Nursing; United States; article; bibliographic database; dept.nur; educational model; human; medical information system; nursing organization; organization and management; peer-reviewed; teaching

The knowledge patients impart - Green, C.A. (Clinical Journal of Oncology Nursing, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: Death; Humans; Knowledge; Nurse-Patient Relations; Patients; dept.nur; human; knowledge; nurse patient relationship; patient

Nursing Students' Use of Electronic and Social Media: Law, Ethics, and E-Professionalism - Westrick, S.J. (Nursing Education Perspectives, 2016)
AIM This article discusses the promotion of professionalism in nursing students with regard to the use of electronic and social media. BACKGROUND Misuse of social media can lead to disciplinary actions and program dismissal for students and to legal actions and lawsuits for nursing programs. Programs are concerned about breaches of patient confidentiality and release of private or inappropriate information that jeopardizes clinical placements and relationships. METHOD The American Nurses Association Code of Ethics and National Council of State Boards of Nursing social media guidelines provide a foundation for promoting e-professionalism in students. Recent law cases involving students who were dismissed from nursing programs due to social media misuse are analyzed. CONCLUSION Schools need policies that clearly establish expectations and the consequences of misuse of social media platforms. Lessons learned from the legal cases presented provide further guidance for both nursing students and nursing programs. © 2016 Lippincott Williams & Wilkins.
31 citations (Crossref) [2023-10-31]
Keywords: Attitude to Computers; Confidentiality; Guidelines as Topic; Humans; Legal and Ethical Issues; Nursing Education; Nursing Students; Professionalism; Social Media; Social Media Policy; Students; Nursing; United States; attitude to computers; confidentiality; dept.nur; ethics; expectation; human; human experiment; law suit; legislation and jurisprudence; nursing education; nursing organization; nursing student; peer-reviewed; practice guideline; professionalism; psychology; social media; standards

Performing pediatric eye exams in primary care - Martin, E.F. (Nurse Practitioner, 2017)
Early vision care is critical for all children. If undetected, eye disorders such as amblyopia and strabismus may result in permanent vision loss. Vision exams should include a careful history and physical including fix and follow, red reflex, and cover/uncover testing. Photo screening and visual acuity exams should be administered whenever possible. © 2017 Wolters Kluwer Health, Inc. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: Adolescent; Child; Child; Preschool; Eye Diseases; Humans; Infant; Infant; Newborn; Physical Examination; Primary Health Care; Vision Screening; adolescent; amblyopia; child; children; dept.nur; eye disease; eye exam; human; infant; newborn; nursing; pediatric patients; peer-reviewed; physical examination; preschool child; primary health care; strabismus; vision exam; vision test; well-child exam

Make America wait again - Petrovic, K. (Journal of International Women's Studies, 2017)
As a means of redirecting my own personal grief that stemmed from Hillary Rodham Clinton's loss to Donald J. Trump in the most recent presidential election, I penned the following prose during the early morning hours of November 9, 2016 as Trump gave his victory speech. Like many Americans who voted in the 2016 Presidential Election, I support the right to vote for one's choice of presidential candidate; however, I am not alone in my concerns about the current presidential administration. Not only are Trump's attempts to silence the media and the right to freedom of speech cause for alarm, but his ideas on healthcare, human rights and international political relationships arguably contribute to apprehension and unease for any number of people. No presidency is without its issues, but the verse penned here may speak to others as the Trump presidency continues to unfold. © 2017 Journal of International Women's Studies.
Keywords: Donald trump; Hillary rodham clinton; United States of America; Woman president; dept.nur; ⛔ No DOI found

The benefits of taekwondo training for undergraduate students: A phenomenological study - Petrovic, K. (Societies, 2017)
The purpose of this phenomenological research was to discover whether training in the Korean martial art of Taekwondo may benefit undergraduate (UG) students in handling stress. The goal of this innovative approach to learning and stress management was to allow UG students from across disciplines at a metropolitan university achieve an increased sense of emotional balance, inner peace, and overall well-being in body, mind, and spirit. No such study has been conducted before now. This research was multidisciplinary in its inclusion of insights from the tenets of higher education, human development and psychology, nursing and sociology, as well as the art, philosophy, and sport of Taekwondo. Ten UG student participants were sought for this research study, though a total of eight students agreed to participate. The study was open to all of the UG students at this university. Phenomenology was used to identify themes that emerged regarding student participant’s experience with stress. Consequently, new ideas were established about the ways in which UG students learned to use Taekwondo training to overcome stress, thereby improving upon and maintaining health and well-being in body, mind, and spirit. © 2017 by the author; licensee MDPI, Basel, Switzerland.
13 citations (Crossref) [2023-10-31]
Keywords: Higher education; Holistic health; Human development; Stress; Taekwondo; Undergraduate students; dept.nur

Examining changes to statewide NP practice in Connecticut - Kazer, M.W.; O'Sullivan, C.K.; Leonard, M. (Nurse Practitioner, 2018)
In 2014, Connecticut legislators eliminated the need for advanced practice registered nurses with 2,000 practice hours to obtain collaborative practice agreements with physicians. This study examined resulting practice changes, barriers, and suggestions for improved implementation of independent practice. Thirteen NPs participated in focus groups to share their experiences and recommendations. © 2018 Wolters Kluwer Health, Inc. All rights reserved.
2 citations (Crossref) [2023-10-31]
Keywords: APRNs; Advanced practice registered nurses; Collaborative practice agreements; Connecticut; Female; Focus Groups; Full-practice authority; Humans; Independent practice; Male; Middle Aged; Nurse Practitioners; Practice Patterns; Nurses'; article; dept.nur; female; human; information processing; legislation and jurisprudence; male; middle aged; nurse practitioner; nursing practice; peer-reviewed; psychology; registered nurse

Urticaria multiforme: A case study - Maynard, K. (Journal of the Dermatology Nurses' Association, 2018)
Urticaria multiforme is a rare, hypersensitivity reaction that occurs in infants and small children. Because of its rare occurrence, many providers are unable to accurately identify the rash and associated symptoms to unnecessary laboratory and histological testing or misdiagnosis. This article highlights the case of an 11-month-old female infant with urticaria multiforme. It explores the identification, diagnosis, and current treatment recommendations. © 2018 Dermatology Nurses' Association.
2 citations (Crossref) [2023-10-31]
Keywords: Article; Hypersensitivity Reaction; Pediatric Rash; Urticaria Multiforme; amoxicillin; amoxicillin plus clavulanic acid; anamnesis; antibiotic therapy; case report; cefdinir; cetirizine; clinical article; dept.nur; diphenhydramine; face edema; female; foot edema; hand edema; human; infant; otitis media; papule; peer-reviewed; physical examination; priority journal; pruritus; rash; urticaria multiforme

Implementing post-discharge 48-hour scripted call for patients with heart failure: An evidence-based practice quality improvement project - Ruggiri, J.C.; Milner, K.A.; Buonocore, D. (MEDSURG Nursing, 2019)
Post-discharge call programs are a simple and effective way to identify and intervene for patient care issues that may occur after discharge. Nurses play a key role in these programs and can lead quality improvement projects on their units to improve patient care during the transition from hospital to home. © 2019, Anthony J. Jannetti Publications, Inc.. All rights reserved.
Keywords: dept.nur; peer-reviewed; ⛔ No DOI found

Beyond the Pain - Green, C. (Research Anthology on Nursing Education and Overcoming Challenges in the Workplace, 2021)
Healthy workplaces promote inclusionary behaviors. When nurses experience exclusionary behaviors such as bullying and incivility, there may also be hidden issues with acceptance of diversity in the workplace environment. Educating nursing staff on the importance of variations in age, culture, gender, sex, race, ethnicity, and religion in the workplace can help facilitate communication among staff. For example, organizations can use educational forums to discuss how different cultures vary in the addressing of conflict within the workplace; some cultures may prefer to reach consensus rather than be confrontational. Chapter 5 discusses strategies that nurses and organizations can implement, such as Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS). TeamSTEPPS is a curriculum that can be used to improve teamwork skills, communication, and build team collaboration. © 2021, IGI Global.
Pages: 402-417 tex.document_type: Book Chapter tex.source: Scopus
Keywords: dept.nur

And sometimes, we say good night - Green, C. (International Journal of Africa Nursing Sciences, 2022)
The evolution of life is that one day after we are born, we must say good night, and fall asleep and breath no more. The trepidation of death is more than the ceasing of lung, cardiac, and brain function; for the nurse who loses a nurse colleague, it is a farewell of a collegial relationship that developed in the process of healing others. The death of a nurse colleague is sacred. © 2022
0 citations (Crossref) [2023-10-31] tex.art_number: 100400 tex.author_keywords: Bereavement; End-of-life care; Grief; Nurse colleague; Sacred tex.document_type: Article tex.source: Scopus
Keywords: article; bereavement; brain function; breathing; dept.nur; grief; heart function; human; lung function; night; nurse; peer-reviewed; terminal care

Applying the nightingale pledge in reducing health disparities: A hospital-acquired pressure injury case study - Green, C. (Advances in skin & wound care, 2022)
ABSTRACT: Professional nurses, by virtue of their training, pledge to care for individuals who are sick or infirm. This commitment is confirmed via the Nightingale Pledge, which focuses on public health and equity and deems the nurse to be a missioner of health. Health disparities exist in direct conflict with the nursing responsibility of caritas, or love. Accordingly, it is imperative that nurse educators create learning environments that are conducive to comfortably discussing differences in physical assessments performed on diverse populations as part of their work to eliminate health disparities and in accordance with the Nightingale Pledge. Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] tex.document_type: Article tex.pubmed_id: 35188485 tex.source: Scopus
Keywords: Hospitals; Humans; dept.nur; hospital; human; peer-reviewed

The Effects of a Deliberate Practice Debriefing During a Response to Rescue Patient Simulation With Undergraduate Nursing Students - Aronson, Barbara; Bell, Arleigh; Andrighetti, Tia; Meyer, Mary; Shepherd, Karen; Bambini, Deborah (Nursing Education Perspectives, 2021)
The purpose of this multisite, randomized, pretest/posttest quasi-experimental study was to compare student nurse competency, learning retention, and perceived student support after exposure to a deliberate practice debriefing versus standardized debriefing. Fifty undergraduate students participated in the complex response to rescue simulation. The intervention group had significantly higher total mean and three subscale scores on the competency tool than the comparison group, although differences in learning retention and student support were not significant. This study provides preliminary support for the effectiveness of deliberate practice debriefing to enhance students’ mastery of skills and behaviors in complex simulations.
0 citations (Crossref) [2023-10-31]
Keywords: Baccalaureate; Clinical Competence; Education; Humans; Nurses; Nursing; Patient Simulation; Simulation Training; Students; clinical competence; dept.nur; human; nurse; nursing education; nursing student; patient simulation; peer-reviewed; simulation training

Cognitive behavioral therapy to sustain the antidepressant effects of ketamine in treatment-resistant depression: A randomized clinical trial. - Wilkinson, Samuel T.; Rhee, Taeho Greg; Joormann, Jutta; Webler, Ryan D.; Lopez, Mayra Ortiz; Kitay, Brandon M.; Fasula, Madonna K.; Elder, Christina; Fenton, Lisa R.; Sanacora, Gerard (Psychotherapy and Psychosomatics, 2021)
Introduction: Ketamine has emerged as a rapid-acting antidepressant. While ongoing treatment can prevent relapse, concerns exist regarding long-term exposure. Objective: We conducted a randomized trial to examine the feasibility and efficacy of cognitive behavioral therapy (CBT) following intravenous ketamine in treatment-resistant depression (TRD). Methods: Subjects with TRD were recruited and treated with 6 intravenous infusions of ketamine over 3 weeks. Subjects who experienced a clinical response (≥50% improvement in depression severity) were then randomized to receiving CBT or treatment as usual (TAU) for an additional 14 weeks, using a sequential treatment model. Results: Of the 42 patients who signed consent, 28 patients achieved a response and were randomized to CBT or TAU. When measured using the Montgomery-Asberg Depression Rating Scale (primary outcome measure), the effect size at the end of the study was moderate (Cohen d = 0.65; 95% CI -0.55 to 1.82), though the group-by-time interaction effect was not significant. There was a significant group-by-time interaction as measured by the Quick Inventory of Depressive Symptomatology (F = 4.58; p = 0.033), favoring a greater sustained improvement in the CBT group. This corresponded to a moderate-to-large effect size of the Cohen d = 0.71 (95% CI -0.30 to 1.70) at the end of the study (14 weeks following the last ketamine infusion). In a subset of patients (N = 20) who underwent cognitive testing using the emotional N-back assessments before and after ketamine, ketamine responders showed improvement in the accuracy of emotional N-back (t[8] = 2.33; p ¡ 0.05) whereas nonresponders did not (t[10] ¡1; p ns). Conclusions: This proof-of-concept study provides preliminary data indicating that CBT may sustain the antidepressant effects of ketamine in TRD. Further study and optimization of this treatment approach in well-powered clinical trials is recommended. © 2021 S. Karger AG, Basel. Copyright: All rights reserved.
36 citations (Crossref) [2023-10-31]
Keywords: Antidepressive Agents; Article; Cognitive Behavioral Therapy; Depression; Depressive Disorder; Humans; Ketamine; Major; Treatment Outcome; Treatment-Resistant; adult; antidepressant activity; antidepressant agent; clinical article; clinical effectiveness; clinical outcome; cognitive behavioral therapy; continuous infusion; controlled study; depression; dept.nur; female; human; ketamine; major depression; male; peer-reviewed; prophylaxis; prospective study; randomized controlled trial; relapse; treatment outcome; treatment resistant depression

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
2 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34670106/
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed

Examining and Solving Health Disparities in the United States: Emerging Research and Opportunities - Green, Cheryl (Medical Information Science Reference, 2021)
"This book provides awareness and discussion on the topic of inequities in healthcare that impact health disparities"–
Keywords: Health status indicators; United States; Health Status Disparities; Healthcare Disparities; United States; Health services accessibility; dept.nur; economics; Health Services Accessibility; economics; Socioeconomic Factors; Minority Health; United States; faculty_collection

The search for support and healing - Green, Cheryl (Research Anthology on Nursing Education and Overcoming Challenges in the Workplace, 2021)
Chapter 6 provides nurses, nurse leaders, and organizations interventions to understand, confront, and eliminate bullying and incivility from the workplace. Emotional intelligence (EI) and cognitive rehearsal are techniques when taught to nurses via in-services provided by organizations, can build awareness of verbal and nonverbal cues used in their communication as well as those of others. By understanding how we communicate and respond to others and vice versa, insight to what are appropriate and inappropriate responses can hold nurses accountable to how they treat one another. The neuroscience of oxytocin release at a biochemical level supports the benefits of organizations investing in the mental and physical health of their employees by empowering them to grow individually and as a collaborative team. © 2021, IGI Global.
Keywords: dept.nur

Strategies for enhancing student learning by managing ambiguities in clinical settings. - Taylor, P.A. (Nurse educator, 2000)
Have you ever watched as care providers, be they student nurses or staff nurses, display behaviors that seem to indicate that they are becoming overwhelmed by situations in the acute care setting? Have you also observed other providers who seem to thrive on the "challenges" presented by these same situations? The same situation stimulates responses that reflect opposite ends of a continuum, the continuum of tolerance of ambiguity. The nurse educator needs to develop a greater understanding of the elements in the clinical situation (the ambiguities) that have stimulated the behavioral responses, and how an individual's level of tolerance of ambiguity influences reactions to the ambiguous situations. These understandings provide the nurse educator with the foundation for developing teaching strategies to facilitate effective management of ambiguous situations in clinical settings.
5 citations (Crossref) [2023-10-31]
Keywords: *Burnout; Professional/pc [Prevention & Control]; *Education; Nursing/mt [Methods]; *Nurses/px [Psychology]; *Teaching/mt [Methods]; Burnout; Professional; Education; Nursing; Humans; Nurses; Nursing Process; Teaching; article; burnout; dept.nur; human; methodology; nurse; nursing education; nursing process; psychological aspect; teaching

Care of the adult patient with cystic fibrosis. - Aronson, Barbara S; Marquis, Melissa (Medsurg nursing : official journal of the Academy of Medical-Surgical Nurses, 2004)
Recently published consensus statements and conference proceedings from the Cystic Fibrosis Foundation provide new direction with regard to the etiology, diagnosis, and treatment of the adult patient with cystic fibrosis (CF). Survival has improved through early diagnosis and improved treatment, and aggressive management of complications. The current state of knowledge, the most recent evidence-based treatment options, and essentials of nursing care for the adult patient with CF are outlined.
Place: United States Aronson, Barbara S. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Cystic Fibrosis/th [Therapy]; Adult; Age Factors; Cystic Fibrosis; Cystic Fibrosis/di [Diagnosis]; Cystic Fibrosis/ep [Epidemiology]; Cystic Fibrosis/et [Etiology]; Diabetes Mellitus; Diabetes Mellitus/et [Etiology]; Diabetes Mellitus/pc [Prevention & Control]; Female; Gastrointestinal Diseases; Gastrointestinal Diseases/et [Etiology]; Gastrointestinal Diseases/pc [Prevention & Control]; Genetic Predisposition to Disease; Genetic Predisposition to Disease/ge [Genetics]; Humans; Infection Control; Infection Control/mt [Methods]; Longevity; Nurse's Role; Phenotype; Reproductive Medicine; Reproductive Medicine/mt [Methods]; Respiratory Therapy; Respiratory Therapy/mt [Methods]; Respiratory Tract Infections; Respiratory Tract Infections/et [Etiology]; Respiratory Tract Infections/pc [Prevention & Control]; Terminal Care; Terminal Care/mt [Methods]; adult; age; artificial ventilation; case report; cystic fibrosis; dept.nur; diabetes mellitus; female; gastrointestinal disease; genetic predisposition; genetics; human; infection control; longevity; methodology; nurse attitude; phenotype; reproduction; respiratory tract infection; review; terminal care; ⛔ No DOI found

Too toxic - Saccomano, Scott; Deluca, Deborah A (Nursing management, 2008)
Firm up on the facts and considerations associated with acetaminophen toxicity.
1 citations (Crossref) [2023-10-31] Place: United States Saccomano, Scott. Southern Connecticut State University Department of Nursing, New Haven, Conn, USA.
Keywords: *Acetaminophen/po [Poisoning]; *Analgesics; Non-Narcotic/po [Poisoning]; *Liver Failure; Acute/ci [Chemically Induced]; Acetaminophen; Acetaminophen/pk [Pharmacokinetics]; Analgesics; Non-Narcotic; Analgesics; Non-Narcotic/pk [Pharmacokinetics]; Antidotes; Drug Overdose/nu [Nursing]; Drug Overdose/pp [Physiopathology]; Drug Overdose/th [Therapy]; Humans; Liver Failure; Acute; Liver Failure; Acute/nu [Nursing]; Liver Failure; Acute/pp [Physiopathology]; Liver Failure; Acute/th [Therapy]; Overdose; Patient Education as Topic; Sorption Detoxification; Sorption Detoxification/mt [Methods]; analgesic agent; antidote; chemically induced disorder; dept.nur; detoxification; human; intoxication; liver failure; methodology; nursing; paracetamol; pathophysiology; patient education; peer-reviewed; review

Enhancing evidence bases for interventions in a baccalaureate program. - Aronson, Barbara S; Rebeschi, Lisa M; Killion, Susan Westrick (Nursing education perspectives, 2007)
Modifying the sequence, objectives, and research-based content for a nursing interventions course in a baccalaureate curriculum resulted in improved outcomes including enhancement of the evidence bases for nursing interventions. A mixed methods research study demonstrated better student preparation for clinical experiences and improved satisfaction with course content, consistency, and sequencing. Faculty reported improved integration of theory, research, and practice. Although grades were slightly lower in the new course, the positive outcomes greatly outweighed this expected finding. A foundation for improving the evidence bases for future nursing practice is guided by the curricular modifications described in this article.
Place: United States Aronson, Barbara S. Department of Nursing, Southern Connecticut State University, New Haven, USA. aronsonb1@southernct.edu
Keywords: *Attitude of Health Personnel; *Curriculum; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Evidence-Based Medicine/ed [Education]; *Nursing Research/ed [Education]; *Students; Nursing/px [Psychology]; Attitude of Health Personnel; Clinical Competence; Connecticut; Curricular and course development; Curriculum; Curriculum/st [Standards]; Diffusion of Innovation; Education; Nursing; Baccalaureate; Evidence-Based Medicine; Evidence-based interventions; Faculty; Nursing; Focus Groups; Health Knowledge; Attitudes; Practice; Health Services Needs and Demand; Humans; Nursing Education Research; Nursing Methodology Research; Nursing Research; Organizational Objectives; Program Evaluation; Qualitative Research; Questionnaires; Skills laboratory; Student learning outcomes; Students; Nursing; Surveys and Questionnaires; United States; article; attitude to health; clinical competence; curriculum; dept.nur; education; evaluation; evidence based medicine; health care quality; health personnel attitude; health service; human; information processing; mass communication; nursing education; nursing methodology research; nursing research; nursing student; organization; organization and management; peer-reviewed; psychological aspect; qualitative research; questionnaire; standard; ⛔ No DOI found

Registered nurses and delegation. - Saccomano, Scott J (The Pennsylvania nurse, 2007)
Place: United States Saccomano, Scott J. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Delegation; Professional/og [Organization & Administration]; *Nursing Assistants/og [Organization & Administration]; *Nursing Staff/og [Organization & Administration]; *Nursing; Supervisory/og [Organization & Administration]; American Nurses' Association; Clinical Competence; Delegation; Professional; Humans; Licensure; Nursing; Nurse's Role; Nurses' Aides; Nursing Assistants/ed [Education]; Nursing Staff; Nursing; Supervisory; Practice Guidelines; Practice Guidelines as Topic; Professional Autonomy; United States; clinical competence; dept.nur; education; human; licensing; medical society; nurse attitude; nursing; nursing assistant; nursing staff; organization and management; practice guideline; professional delegation; professional practice; review; ⛔ No DOI found

Assessment of nursing student's learning outcomes and employment choice after the implementation of a senior capstone course. - Rebeschi, Lisa; Aronson, Barbara (International journal of nursing education scholarship, 2009)
Many undergraduate baccalaureate nursing programs incorporate clinical emersion courses at the end of the program. Nursing capstone courses have become increasingly important in facilitating student transition into practice. However, little is known regarding the overall effectiveness of this teaching model for students, nursing programs, and clinical agencies. Previous studies revealed conflicting results about the benefits of a senior level precepted clinical experience. In this multi-method study, the authors examined student learning outcomes, perceptions, employment choice and retention following implementation of a new capstone nursing course. Results of this study indicated that a capstone course does not necessarily significantly improve scores on achievement exams or NCLEX RN first time pass rates. Nevertheless, qualitative content analysis revealed the following themes: integration, autonomy, confidence, authority, and advocacy consistent with a perceived enhanced competence in the nursing role. Data indicated that graduates often seek employment and remain at their capstone site or within their capstone specialty.
12 citations (Crossref) [2023-10-31] Place: Germany Rebeschi, Lisa. Southern Connecticut State University, USA.
Keywords: *Attitude of Health Personnel; *Choice Behavior; *Clinical Competence; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Employment/px [Psychology]; *Students; Nursing/px [Psychology]; Adult; Attitude of Health Personnel; Capstone; Choice Behavior; Clinical Competence; Clinical Competence/st [Standards]; Clinical teaching; Education; Nursing; Baccalaureate; Employment; Female; Humans; Licensure; Nursing; Male; Middle Aged; Models; Educational; Models; Nursing; New England; Nurse's Role; Nurse's Role/px [Psychology]; Nursing Education Research; Nursing Methodology Research; Nursing education; Personnel Turnover; Personnel Turnover/sn [Statistics & Numerical Data]; Preceptorship; Preceptorship/og [Organization & Administration]; Professional Autonomy; Program Development; Program Evaluation; Qualitative Research; Self Efficacy; Students; Nursing; United States; Use of preceptors; adult; article; clinical competence; decision making; dept.nur; education; educational model; employment; evaluation; female; health care quality; health personnel attitude; human; licensing; male; middle aged; model; nurse attitude; nursing education; nursing methodology research; nursing student; organization and management; personnel management; professional practice; program development; psychological aspect; qualitative research; self concept; standard; statistics

Review: Depressive symptoms and fatigue as mediators of relationship between poor sleep factors and medication adherence in HIV-positive women. - Petrovic, Kimberly (Journal of Research in Nursing, 2015)
0 citations (Crossref) [2023-10-31] Place: (C)2015Sage Publications
Keywords: dept.nur

Creutzfeldt-Jakob disease. Assessment and management update. - Wallace, M. (Journal of gerontological nursing, 1999)
3 citations (Crossref) [2023-10-31]
Keywords: *Creutzfeldt-Jakob Syndrome/nu [Nursing]; Aged; Creutzfeldt Jakob disease; Creutzfeldt-Jakob Syndrome; Creutzfeldt-Jakob Syndrome/cl [Classification]; Creutzfeldt-Jakob Syndrome/pp [Physiopathology]; Creutzfeldt-Jakob Syndrome/px [Psychology]; Humans; MLCS; MLOWN; Male; Middle Aged; Nursing Assessment; Nursing Assessment/mt [Methods]; Patient Care Planning; Prognosis; Risk Factors; aged; case report; classification; dept.nur; human; male; methodology; middle aged; nursing; nursing assessment; pathophysiology; patient care planning; prognosis; psychological aspect; review; risk factor

Meeting the learning needs of diverse students in BSN programs. - Thompson, C (Nurse educator, 1998)
4 citations (Crossref) [2023-10-31] Place: United States Thompson, C. Department of Nursing, Southern Connecticut State University, New Haven, USA.
Keywords: *Cultural Diversity; *Education; Nursing; Baccalaureate/mt [Methods]; *Students; Nursing; Cultural Diversity; Education; Nursing; Baccalaureate; Humans; Learning; MLCS; MLOWN; Students; Nursing; article; cultural anthropology; dept.nur; human; learning; methodology; nursing education; nursing student

Complexity science, nursing, and COVID-19 - White, Kenneth R.; Begun, James W.; Vicenzi, Angela E (The American journal of nursing, 2021)
Understanding a bewildering crisis like a pandemic as 'normal' may be empowering. Copyright © 2021 Wolters Kluwer Health, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103432985
Keywords: COVID-19; Health Policy; Humans; Nurse's Role; Systems Analysis; dept.nur; epidemiology; health care policy; human; nurse attitude; peer-reviewed; system analysis; therapy

The hollow: A theory on workplace bullying in nursing practice - Green, C. (Nursing Forum, 2021)
Background: Incivility and bullying within the profession of nursing remains a problem within the workplace. As a result, healthcare workplaces can become unhealthy and difficult for nurses to function within. Work productivity is impacted and patients' healthcare is placed at risk when nurses are emotionally and physically affected by workplace incivility and bullying. Clinical nurse leaders (CNLs) applying theoretical reasoning and nursing competencies' in addressing bullying and incivility within the workplace, can provide an organized and effective organizational approach to addressing bullying and incivility in work environments. Methods: Theoretical reasoning and nursing competencies in addressing bullying and incivility within the workplace, will be examined as a means to identify nurses exhibiting signs and symptoms of bullying and incivility in work environments. The theory of The Hollow will identify the origins of affected nurses' behaviors and the physiological and psychological impact of bullying and incivility. The CNL role will be used as a facilitator of change at the microsystem level. And competencies for addressing behaviors associated with bullying and incivility will be addressed. Approach: Innovation adapted from prior research and literature developed by the author, extrapolated from the literature on workplace bullying and incivility in nursing practice. Outcomes: Bullying and incivility can be resolved in the workplace when competencies are set forth by nursing leaders to educate and empower nursing staff on expectations of healthy work environments. Conclusion: Healthy workplaces are achievable when nurse leaders, such as CNLs, educate and empower nurses to have the expectation of healthy work environments not only for themselves, but for all nurses. © 2020 Wiley Periodicals LLC
6 citations (Crossref) [2023-10-31] tex.author_keywords: bullying; clinical nurse leader; incivility; nurses; the hollow tex.coden: NUFOA tex.document_type: Article tex.pubmed_id: 33350483 tex.source: Scopus
Keywords: Bullying; Humans; Incivility; Nurses; Workplace; article; bullying; clinical nurse leader; dept.nur; expectation; human; incivility; leadership; nurse; nurses; nursing practice; nursing staff; peer-reviewed; reasoning; the hollow; theoretical study; work environment; workplace

Evaluation of an innovative curriculum enhancement: The conversation project - Pagano, Michael; Manger, Diana R.; O'Shea, Eileen; O'Sullivan, Cynthia (Nursing Education Perspectives, 2020)
Two northeast nursing schools piloted an innovative curriculum to teach The Conversation Project (TCP) to the next generation of nurses. The goal was to educate 26 graduate nursing students about how to have end-of-life and advance care planning conversations with people before they experience a crisis. The focus of assignments was on communicating newly learned TCP information. Postreflections demonstrated that participants felt their communication skills had been enhanced while their anxieties were reduced. The students' abilities to have end-of-life conversations increased. © Lippincott Williams & Wilkins.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85094221077
Keywords: Advance Care Planning; Communication; Conversation Project; Curriculum; End-of-Life Care; Graduate Nursing Education; Humans; Learning; Schools; Nursing; Students; Nursing; adult; advance care planning; anxiety; article; clinical article; communication skill; conversation; curriculum; dept.nur; female; graduate nursing student; human; interpersonal communication; learning; male; nursing education; nursing student; peer-reviewed

Reducing Student Nurse Stigmatization of the Patient Who Misuses Opioids A Scoping Review - Maynard, Kristi (Journal of Addictions Nursing, 2020)
The United States is in the midst of an opioid epidemic. The numbers of opioid-related deaths have been steadily climbing, magnifying the need for innovative intervention. Stigma is a set of preconceived, negative assumptions about a patient population or group. Stigma is a known deterrent to communication and the delivery of healthcare. Nurses serve as a primary contact for many marginalized patients within the healthcare system. The purpose of this scoping review is to gather known data on the use of educational interventions with nursing students to reduce stigmatizing tendencies. Inclusion criteria constituted an educational intervention involving student nurses and an effort to reduce stigmatizing attitudes toward patients who misuse opioids. The intervention must have taken place in an institute of higher learning between the years of 2003 and 2018. Exclusion criteria included community-wide studies. A single study was identified addressing nursing student reduction of stigmatization of the individual who uses opioids, and so, the search was expanded to include any student nursing intervention developed to reduce stigma toward any marginalized population. The following electronic databases were utilized in the search process: Cumulative Index of Nursing and Allied Health Literature, Google Scholar, Journal Storage, Microsoft Academic, and ScienceDirect. Reference pages of selected or related articles were reviewed in an attempt to identify additional pertinent literature through citation mapping. Fifteen studies were identified, each of which utilized a variable methodology for stigma reduction with varying levels of success. © Lippincott Williams & Wilkins.
3 citations (Crossref) [2023-10-31] WOS:000526707500008
Keywords: Attitude of Health Personnel; Clinical Competence; Humans; Opioid-Related Disorders; Social Stigma; Stereotyping; Students; Nursing; clinical competence; dept.nur; education; health personnel attitude; human; nurse; nursing student; opiate addiction; opioid misuse; peer-reviewed; psychology; social stigma; stereotyping; stigma; student

Equity, achievement, and thriving in nursing academic progression - Aragon, Sofia; Beauvais, Audrey M.; Friday, Vivienne; Green, Cheryl; Kiger, Anna J.; King, Simmy; Lear, Tina; Mahowald, Jane; McGuill, Gail; Perkins, Danielle; Valdez, Anna Maria; Velasco, Brian; et al. (Teaching and Learning in Nursing, 2020)
8 citations (Crossref) [2023-10-31] tex.ids: aragonEquityAchievementThriving2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088786114 type: Article
Keywords: dept.nur; equity; nursing education; peer-reviewed; progression

Nurses and Patients' Perspectives on Spiritual Health Assessment - Green, Cheryl (Journal of Religion & Health, 2020)
Nurses conduct physical and psychosocial assessments during admissions to healthcare facilities. Patients rely upon nurses to provide support and education during their journey, from periods of health decline to states of optimal wellness. Therefore, nurses are an ideal population to assess spiritual health. The value and necessity of spiritual assessment were explored on an inpatient unit providing medical and palliative care to patients. Two spiritual assessment tools, comprised each of five items, were evaluated by nursing staff and patients. Spiritual Assessment Tool 1 used language that was unaffiliated with religion, nor a belief in God, and Spiritual Assessment Tool 2 used language affiliated with faith and belief in God. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
2 citations (Crossref) [2023-10-31] WOS:000584350300004
Keywords: Attitude of Health Personnel; Humans; Nursing Staff; Palliative Care; Patients; Religion; Spirituality; adult; article; dept.nur; health personnel attitude; hospital patient; human; language; nursing staff; palliative therapy; patient; peer-reviewed; religion

Editorial for special collection: Current issues and practices in school nursing - Resha, Cheryl (SAGE Open Nursing, 2020)
1 citations (Crossref) [2023-10-31] tex.ids: reshaEditorialSpecialCollection2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082958509 type: Editorial
Keywords: dept.nur; peer-reviewed

Enough Is Enough: Confronting Workplace Bullying and Incivility - Green, Cheryl Ann (STTI, 2020)
tex.ids: greenEnoughEnoughConfronting2020
Keywords: dept.nur; ⛔ No DOI found

High-technology and hospice home care. Strange bedfellows - Hays, J.C. (Nursing Clinics of North America, 1988)
Technologic advances are changing hospice home care. A case study explores the clinical dilemmas and illustrates the educational and research agendas required to resolve them.
Keywords: Adult; Case Report; Female; Home Care Services; Hospices; Human; Patient Care Planning; Patient Care Team; Technology; High-Cost; Terminal Care; United States; computer analysis; dept.nur; home care; hospice; medical technology; organization and management; review; technical aid; united states; ⛔ No DOI found

Hospice policy and patterns of care - Hays, Judith C (Journal of Nursing Scholarship, 1986)
Hospice providers and policy makers are currently evaluating the emerging patterns of hospice care, especially regarding cost containment considerations. This study compared patterns of care for two groups of hospice homecare clients–one group, which received only homecare services for the duration of the hospice career; the other, which received both hospice homecare and inpatient services. The groups were significantly different on clinical parameters, number of homecare episodes, survival rate, and place of death. The impact of policy structures on continuity of care and service equity are discussed. Copyright © 1986, Wiley Blackwell. All rights reserved
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/004-901-078-522-073 tex.type: [object Object]
Keywords: Aged; Comparative Study; Connecticut; Cost Control; Female; Home Care Services; Hospices; Hospitalization; Human; Male; Middle Age; Public Policy; United States; adult; aged; article; comparative study; cost control; dept.nur; economics; female; home care; hospice; hospitalization; human; male; organization and management; policy; utilization review

Critical thinking skills of baccalaureate nursing students at program entry and exit - Thompson, C; Rebeschi, LM (Nursing and Health Care Perspectives, 1999)
Most nurse educators would agree that critical thinking is an essential competency for the professional nurse in today's ever-changing health care environment. In fact, critical thinking has been identified as an integral component of professional nursing practice and has been incorporated in accreditation guidelines (1-3). As a result of this imperative, professional programs of nursing must explicate a clear definition of critical thinking, identify specific learning outcomes reflective of critical thinking abilities, and select appropriate ways to measure the achievement of these outcomes in graduating students. Although much has been written about the need for critical thinking skills, the concept and measurement of critical thinking within the context of nursing education has not yet been clearly defined (4-6). As a result, nursing programs are developing their own conceptual definitions of critical thinking and using a variety of methods to measure outcomes (5). The authors caution that to ensure validity of findings, the instruments used must reflect the individual program's definition of the concept. In most cases, outcomes have been assessed using a cross-sectional design that compares students at different levels or types of programs or are measured as an end-of-program outcome. While such designs can provide educators with knowledge of students' critical thinking abilities at a particular point in the educational process, longitudinal data are needed to assess the effects of the educational program.
tex.unique-id: ISI:000085103900006
Keywords: *Clinical Competence/st [Standards]; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Educational Measurement/mt [Methods]; *Nursing Process; *Program Evaluation/mt [Methods]; *Students; Nursing/px [Psychology]; *Thinking; Accreditation; Clinical Competence; Education; Nursing; Baccalaureate; Educational Measurement; Humans; Nursing Education Research; Nursing Process; Outcome Assessment (Health Care); Outcome Assessment; Health Care; Program Evaluation; Research Design; Students; Nursing; Thinking; accreditation; article; clinical competence; dept.nur; education; health care quality; human; methodology; nursing education; nursing process; nursing student; organization and management; outcome assessment; psychological aspect; standard; thinking; ⛔ No DOI found

Outcomes assessment: implications for nursing education. - Thompson, Cesarina; Bartels, Jean E (Journal of Professional Nursing, 1999)
In response to public criticisms about the outcomes of higher education, colleges and universities have implemented comprehensive assessment programs. In nursing education, outcomes assessment has become a criteria for accreditation. Yet, currently no guidelines exist describing “best practices” in nursing education outcomes assessment. Experts in educational assessment provide helpful guidelines for nurse educators as they establish comprehensive assessment plans. The authors provide a review of the literature in the field of assessment and offer strategies for developing successful assessment programs in nursing education.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/151-849-929-326-658 tex.type: [object Object]
Keywords: *Benchmarking/og [Organization & Administration]; *Education; Nursing/st [Standards]; *Guidelines as Topic; *Outcome Assessment; Health Care/og [Organization & Administration]; *Program Evaluation/mt [Methods]; Accreditation; Accreditation/og [Organization & Administration]; Benchmarking; Curriculum; Education; Nursing; Guidelines; Humans; Nursing education; Outcome Assessment (Health Care); Outcomes assessment; Program Evaluation; Program evaluation; accreditation; curriculum; dept.nur; health care quality; human; methodology; nursing education; organization and management; outcome assessment; practice guideline; quality control; review; standard

Focus on community: directions for nursing knowledge development - Kulbok, Pamela A; Gates, Marie F; Vicenzi, Angela E; Schultz, Phyllis R (Journal of Advanced Nursing, 1999)
Nurses are challenged to advance the theoretical foundations of community practice. This paper offers ideas on what-has been done and what needs to be done to meet this challenge. Within a community health nursing perspective, the paper defines community, proposes an integrated knowledge development framework that focuses on community, analyses contemporary theoretical and philosophical foundations of community in nursing, considers three worldviews in which nursing can be framed, and examines parameters for knowledge development for the future.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-438-110-171-942 tex.type: [object Object]
Keywords: Community; Community Health Nursing; Community health nursing; Humans; Knowledge; Knowledge development; Nursing; Nursing Theory; Nursing theory; Philosophy; Post-modernism; Professional Practice; World-view; article; community health nursing; dept.nur; human; knowledge; nursing; nursing theory; professional practice

Differences in Classroom Teaching Preferences between Traditional and Adult BSN Students - Thompson, C.; Sheckley, B.G. (Journal of Nursing Education, 1997)
The primary purposes of this study were to identify the best teaching practices for adult baccalaureate (BSN) nursing students and to examine if adult students' teaching preferences differed from those of traditional BSN students. The sample consisted of 206 adult and traditional students in four BSN programs. The adult nursing student sample was further subdivided into two groups: adults with no prior nursing education (adult non-nurses) and adults with prior nursing education (RN'S). Using a two-part, self-administered questionnaire, respondents were asked to rate the frequency with which 41 teaching strategies were used in their best and in their worst classroom learning experiences in nursing. In most cases, adult non-nurses' teaching preferences did not vary significantly from the preferences of traditional students. However, adults with no prior nursing education did show a preference for knowledgeable and organized instructors. In contrast RNs' preferred classroom situations were where time on task was emphasized, cooperative learning was encouraged, and expectations for learning were high. Results indicate that classroom teaching preferences vary as a function of prior experience with the subject matter and are not attributable to age itself. Findings suggest that prior experience with course content is a more important consideration in planning programs than generalized adult experience.
26 citations (Crossref) [2023-10-31]
Keywords: *Choice Behavior; *Education; Nursing; Associate; *Education; Nursing; Baccalaureate; *Education; Professional; Retraining; *Students; Nursing/px [Psychology]; *Teaching/st [Standards]; Adolescent; Adult; Choice Behavior; Education; Nursing; Associate; Education; Nursing; Baccalaureate; Education; Professional; Retraining; Factor Analysis; Statistical; Humans; Middle Aged; Nursing Education Research; Questionnaires; Students; Nursing; Surveys and Questionnaires; Teaching; adolescent; adult; article; comparative study; continuing education; decision making; dept.nur; factorial analysis; human; middle aged; nursing education; nursing student; psychological aspect; questionnaire; standard; teaching

Chaos theory and some nursing considerations - Vicenzi, Angela E (Nursing Science Quarterly, 1994)
The alleged synthesis of nursing and public health has not produced the expected community-as-client emphasis. Public health is characterized as disease-focused, with masculine domination, using a causal model. The explanatory model of chaos challenges nurses to reexamine nursing's theoretical base by questioning assumptions associated with linear thinking. The selected chaotic concepts of aperiodicity, attractors, sensitive dependence on initial conditions, phase space, and fractals are discussed here. Each concept's connection to physics and mathematics is cited and considerations for nursing science are outlined. Conclusions include redefining health, nursing, and community in chaotic terms and renaming nursing practice, which has this aperiodic and holistic paradigm, as ecologic health nursing.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-144-108-349-30X tex.type: [object Object]
Keywords: Chaos Theory; Community Health Nursing; Fractals; Human; Models; Nursing; Nonlinear Dynamics; Rogers; Thinking; article; dept.nur; fractal analysis; human; model; nonlinear system; nurse; thinking

Chaos Theory and Nursing Revisited: Commentary and Response - Zbilut, J.P.; Staffileno, B.; Vicenzi, A.E. (Nursing Science Quarterly, 1994)
3 citations (Crossref) [2023-10-31]
Keywords: Human; Nonlinear Dynamics; Nursing Theory; dept.nur; human; nonlinear system; note; nursing; ⛔ No DOI found

Social support systems in elder homebound clients - Zink, Margo R (Home Health Care Management & Practice, 1994)
An individual's social support system comprises multiple networks. A lack in one system may cause an increased need for support in another. Social support has been found to be of vital impor tance to the health of the older adult client and caregiver. It has been found to have a significant influence on health outcomes, acting as a buffer and altering recovery patterns. This article de scribes the concept of social support and relates how the home health care nurse can assess this dimension and use the findings to better plan patient care in the home setting. Key words: social support, home care, older adult. © 1994, Sage Publications. All rights reserved.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-578-813-060-298 tex.type: [object Object]
Keywords: dept.nur

Case commentary: Bass v. Barksdale: implications for public health and home care nurses - Killion, Susan Westrick (Public Health Nursing, 1993)
A recent malpractice case involved public health nurses. Given the legal issues based on this case, recommendations can be made to help ensure legal accountability, improve practice, and minimize liability risk. Areas of concern include doctor's orders and communication relating to telephone orders, the nurse's accountability to the client, documentation and patient teaching, the physician's duty to supervise the nurse, and corporate negligence. The court's analysis of the facts in finding areas of liability can guide nurses in avoiding malpractice litigation.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/039-112-513-700-590 tex.type: [object Object]
Keywords: Community Health Nursing; Ethambutol; Female; Human; Liability; Legal; Malpractice; Nursing Records; Patient Education; Public Health Nursing; Tennessee; United States; Vision Disorders; article; dept.nur; ethambutol; female; human; iatrogenic disease; legal aspect; legal liability; malpractice; medical record; nurse; patient education; public health service; visual disorder

Collaborative project to examine social support in elder homebound diabetics - Zink, Margo R; Gadomski, Mary; Oconnell, Patricia Buckley; Nizziherzog, Marie (Home Health Care Management & Practice, 1992)
Social support has a significant effect on the response to illness and treatment. The au thors present some of the findings and practical applications originating from a collaborative study, including a clinical indicator tool for the diabetic patient. This information gives the home health care professional an expanded knowledgebase to use in developing individualized care plans for the elder home care diabetic. © 1992, Sage Publications. All rights reserved.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-204-733-259-335 tex.type: [object Object]
Keywords: dept.nur

Nurse Manners' Guide to Politically Correct Behavior - Vicenzi, Angela E (Journal of Nursing Scholarship, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-975-520-464-024 tex.type: [object Object]
Keywords: Human; Nurses; Social Behavior; Wit and Humor; article; dept.nur; human; humor; nurse; psychological aspect; social behavior

Family rituals that provide meaning for single-parent families: - Moriarty, Patricia Hale; Wagner, Linda D (Journal of Family Nursing, 2004)
The number of single-parent families has increased dramatically in the United States. The purpose of this study was to explore the types of family rituals present in single-parent families and their meaning within the family context. Little is known about family rituals in single-parent families, and therefore grounded theory was the qualitative research method used for this study. Unstructured face-to-face interviews were used to obtain data from a theoretical sample of seven single parents. Data analysis appropriate to the grounded theory method was utilized to identify a core variable and an emerging theory. Six types of rituals: connection, spiritual, love, recreation, celebration, and evolving were found to be used by these single-parent families as a way to facilitate family cohesion and instill family values. Applicability of the findings of this study are beneficial for nurses working with clients with diverse, changing, and complex social situations such as the single-parent family. © 2004 Sage Publications.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/041-384-923-605-132 tex.type: [object Object]
Keywords: Family health; Qualitative research; Rituals; Single-parent family; dept.nur

Adolescent attitudes, beliefs, and concerns regarding breastfeeding. - Nelson, Antonia M (MCN. The American journal of maternal child nursing, 2009)
Purpose: To investigate the attitudes, beliefs, and concerns of pregnant and postpartum adolescents regarding breastfeeding. Study Design and Methods: Audiotaped focus groups of low-income, largely minority pregnant and postpartum adolescents were conducted and transcripts analyzed using content analysis techniques. Findings: Major themes identified were in the area of beliefs, such as They say it's healthy, or It hurts; attitudes, such as breastfeeding is the mother's choice and The baby comes first; and concerns such as privacy, and Breastfeeding leads to dependency. Clinical Implications: Adolescents can be encouraged to breastfeed, but require appropriate education beyond what they have heard from others. Myths such as pain during breastfeeding need to be addressed. Since teens want to learn but not be told what to do, active learning strategies such as guided Internet searches could be helpful to guide them into discovery of the benefits of breastfeeding. Since all the teens in this study felt that the baby comes first, emphasizing the benefits of breastfeeding for the baby should predominate educational efforts. Concerns related to physical exposure while breastfeeding can be addressed antenatally through discussing creative strategies to maintain modesty. This study suggests that, in the postpartum hospital setting, adopting a sensitive, initially hands-off' approach to supporting breastfeeding might be more well-accepted than tactile assistance, and that following the initial establishment of a milk supply, various levels of breastfeeding exclusivity should be considered as potentially acceptable infant feeding patterns.
17 citations (Crossref) [2023-10-31] Place: United States Nelson, Antonia M. Southern Connecticut State University, New Haven, CT, USA. nelsona13@southernct.edu
Keywords: *Breast Feeding/px [Psychology]; *Health Knowledge; Attitudes; Practice; *Mothers/ed [Education]; *Mothers/px [Psychology]; *Psychology; Adolescent; Adolescent; Adolescent Psychology; Breast Feeding; Breastfeeding; Female; Focus Groups; Focus groups; Health Knowledge; Attitudes; Practice; Health Promotion; Humans; Mothers; Postpartum Period; Postpartum Period/px [Psychology]; Pregnancy; Qualitative research; Young Adult; adolescent; adult; article; attitude to health; breast feeding; child psychology; dept.nur; education; female; health promotion; human; information processing; mother; pregnancy; psychological aspect; puerperium

Antibiotic-taking experiences of undergraduate college students. - Aronson, Barbara S (Journal of the American Academy of Nurse Practitioners, 2006)
Purpose: The purpose of this qualitative descriptive study was to explore the medication-taking experiences of undergraduate college students prescribed short-term antibiotic therapies and to describe factors influencing their adherence. Data sources: Thirty-four undergraduate students prescribed antibiotics for treatment of an acute infectious illness at a large university health center were recruited to participate in this study. Semistructured telephone interviews were conducted after students finished their course of treatment. Qualitative descriptive content analysis was used to analyze the transcripts typed from the audio-taped phone interviews. Conclusions: The main theme that emerged from the data was antibiotic-taking self-management. Most participants were able to adapt medication regimens into their daily routines, and used events in their day and specific reminder strategies to help them to remember to take their medications. This occurred despite an ever-changing class and work schedule and being prescribed complex, lengthy antibiotic regimens. Most dosing errors occurred during times when schedules changed or students were off campus during weekends or college breaks. A small number of students discontinued therapy early because of side effects or forgetfulness. Implications for practice: By understanding factors that influence antibiotic adherence from a college student perspective, healthcare providers can suggest strategies to promote adherence that are tailored to the specific needs of this unique population. © 2006 American Academy of Nurse Practitioners.
6 citations (Crossref) [2023-10-31] Place: United States Aronson, Barbara S. Department of Nursing, Southern Connecticut State University, New Haven, Connecticut 06515, USA. aronsonb1@southernct.edu
Keywords: *Anti-Bacterial Agents/tu [Therapeutic Use]; *Patient Compliance; *Self Care; *Students; Adolescent; Adult; Anti-Bacterial Agents; Antibiotic adherence; College students; Female; Humans; Male; Medication self-management; Patient Compliance; Self Care; Students; United States; adolescent; adult; antiinfective agent; article; dept.nur; female; human; male; patient compliance; self care; student

Calm in Chaos: Prose on Tensions of Hate and Distrust in Society - Green, Cheryl; Green, Joshua William (Westbow Press, 2019)
Keywords: Hate; Poetry; Poetry; Racism; dept.nur; faculty_collection

Challenging case in clinical practice: S-adenosyl methionine for mood support during corticosteroid therapy - Adimando, Andrea (Alternative and Complementary Therapies, 2020)
0 citations (Crossref) [2023-10-31] tex.ids: adimandoChallengingCaseClinical2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086454876 type: Article
Keywords: dept.nur

Narrative orphaned: When grief overwhelms - Green, Cheryl (Journal of Psychiatric and Mental Health Nursing, 2021)
What is known on the subject?: The loss of a parent for an adult can be devastating and can impact other relationships. The adult, in absence of parental love and support, may question their own identity. What this paper adds to existing knowledge?: A narrative is used to explain the adults’ experience of parental death and their new identity of being orphaned. What are the implications for practice?: Increased awareness for adults grieving the loss of a parent(s), as to the normalcy of feeling orphaned Adults grieving the death of a parent(s) are provided resources and support in addressing their grieving process. Abstract: Introduction When a parent dies during their child's adulthood, the life of the adult is altered as the familiarity of parental love and safety changes. The isolation and loneliness penetrates deeply as the orphaned adult must now navigate their world in absence of the most significant people in their lives, their parents. Aim To assist persons affected by parental death in understanding the normalcy of feeling orphaned while grieving. Method The use of a personal narrative to provide mental health support to others. Results The resumption of a routine that existed before parental death is possible, but takes time. Intermittent periods of grief can occur throughout one's life. Discussion When grief interrupts one's ability to function daily and the affected adult has relationships impacted by their parent's death, it is recommended that the adult seek mental health treatment. Implications for Practice Narratives can be used with persons affected by parental loss, to provide an example of normal versus complicated grieving and identify when mental health treatment is needed. © 2020 John Wiley & Sons Ltd
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85084478941
Keywords: Adaptation; Adult; Child; Emotions; Grief; Humans; Loneliness; Mental Health; Parents; Psychological; adult; child; child parent relation; coping behavior; dept.nur; emotion; grief; human; loneliness; mental health; peer-reviewed

Equity and diversity in nursing education - Green, Cheryl (Teaching and Learning in Nursing, 2020)
Retention and development of ethnically diverse nursing students may be more likely to occur when nursing faculty receive training on factors that can impact academic success. By understanding complex school system dynamics in low-income areas, cultural, linguistic, gender, age, religion, and ethnic differences, students’ strengths can be readily recognized, embraced, and encouraged by nursing faculty. When the necessity of equity and diversity is recognized within nursing education, this may potentially translate to retention and completion of nursing programs by nursing students from diverse backgrounds, thereby increasing diversity within the nursing profession. © 2020 Organization for Associate Degree Nursing
14 citations (Crossref) [2023-10-31] tex.ids: greenEquityDiversityNursing2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089451312 type: Article
Keywords: Diversity; Equity; Nursing education; Nursing faculty; Nursing students; academic success; article; dept.nur; ethnic difference; female; gender; human; human experiment; lowest income group; male; nursing education; nursing student; occupation; peer-reviewed; religion

Should nursing be considered a STEM profession? - Green, Cheryl; John, Lori (Nursing Forum, 2020)
Background: The National Science and Technology Council developed a 5-year plan in 2013 to ensure that science, technology, engineering, and mathematics (STEM) experienced sustained growth within the United States (US). Nursing is comprised of multiple sciences that include chemistry, physics, biology, microbiology, anatomy and physiology, pharmacology, and the social and behavioral sciences of sociology, developmental lifespan psychology, and psychology. Science, technology, engineering, and math constitute the traditional STEM acronym. Nursing programs graduate nurses with both the rigorous academic coursework and diverse clinical skills necessary to provide patient care. These skills employed by nurses in the clinical setting can serve as the basis for the inclusion of the nursing profession as a STEM-designated profession by the federal government and educational institutions within the US. Problem: Currently, the US government does not acknowledge the profession of nursing as a STEM-designated profession. Acknowledgment of nursing as a STEM profession could potentially make more funding available for nursing education within the US and address nursing shortages both in clinical and academic settings. As well as position professional nurses for careers not only within the health sector but that of business and industry because of nurses’ STEM knowledge. Hence, enhancing the growth of STEM within the US and creating global market economic competitiveness with new innovation development. Approach: In the practice of nursing, nurses apply the sciences, math, and innovative technology in the assessments, diagnoses, and planning of patients’ care. Nurses implement scientifically-based interventions to treat illness and sustain human life and to ultimately evaluate the outcomes of the care provided to patients. Outcomes: Methodologies of evaluation of outcomes of patient care status post nursing interventions (ie, administration of intravenous antibiotics to treat pneumonia) are based upon rationales that have been derived from evidenced-based practice and nursing research; both originating from applied STEM knowledge. Conclusion: The formal designation by the US federal government, for nursing to be recognized as a STEM profession, can increase funding to the nursing profession and enhance the diversity of employment opportunities for nurses in industry and business. Thereby potentially decreasing nursing shortages and bringing national and worldwide recognition to nursing in both academia, industry, business, and clinical settings, as a profession contributing to the science of improvement of the health of all people through STEM knowledge. © 2019 The Authors. Nursing Forum published by Wiley Periodicals, Inc.
5 citations (Crossref) [2023-10-31] tex.ids: greenShouldNursingBe2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85076273828 type: Article
Keywords: Humans; Professional Role; STEAM; STEM; Science; classification; dept.nur; education; health care; human; inclusion; innovation; nursing; professional standard; science

Facilitating trust engenderment in secondary school nurse interactions with students. - Summach, Anne H J (The Journal of school nursing : the official publication of the National Association of School Nurses, 2011)
School nurses are involved in a complex framework of interactions with students, other professionals, parents, and administrators. Trust between nurse and student is critical for interaction effectiveness. The goal of this study was to understand through phenomenology the process of engendering trust in school nurse-high school student interactions. The qualitative approach explored school nurse perceptions of experiences interacting with students, yielding insights into nurse- and setting-based factors contributing to the development of trust. Subthemes within these included key behaviors and attributes enhancing trust engenderment in school nurse-student interactions. Study findings were well supported by the existing nursing and psychological research literature. Nurses that purposefully strive to develop trust in young people will maximize adolescent health results.
11 citations (Crossref) [2023-10-31] Place: United States Summach, Anne H J. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Nurse-Patient Relations; *Schools/sn [Statistics & Numerical Data]; *Students/px [Psychology]; *Trust/px [Psychology]; Adolescent; Adolescent Behavior; Adult; Clinical Competence; Humans; Nurse-Patient Relations; Patient Satisfaction; Qualitative Research; Schools; Students; Trust; Young Adult; adolescent; adult; article; child behavior; clinical competence; dept.nur; high school; human; nurse patient relationship; patient satisfaction; psychological aspect; qualitative research; role promotion/development; school; school nurse characteristics; school nurse knowledge/perceptions/self-efficacy; statistics; student; trust

Improving sleep-wake disturbances in patients with cancer - Lamberti, Mary Patricia (Clinical Journal of Oncology Nursing, 2014)
Patients with cancer tend to suffer sleep-wake disturbances at a higher rate than the general population. Insomnia and fatigue should be regarded as a significant patient safety issue, as poor sleep can elevate patients' risks of falls, motor vehicle accidents, and acute infectious illnesses. To alleviate those risks, oncology nurses should be familiar with effective evidence-based practices for assessing and improving patients' sleep quality.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-927-422-564-577 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Accidental Falls; Accidents; Traffic; Cancer; Humans; Infection; Interventions; Neoplasms; Patient Safety; Safety; Sleep; Sleep Wake Disorders; complication; dept.nur; falling; human; infection; neoplasm; patient safety; traffic accident

Gaming the system: developing an educational game for securing principles of arterial blood gases - Boyd, Cory Ann; Warren, Jonah; Glendon, Mary Ann (Journal of Professional Nursing, 2016)
This article describes the development process for creating a digital educational mini game prototype designed to provide practice opportunities for learning fundamental principles of arterial blood gases. Mini games generally take less than an hour to play and focus on specific subject matter. An interdisciplinary team of faculty from two universities mentored student game developers to design a digital educational mini game prototype. Sixteen accelerated bachelor of science in nursing students collaborated with game development students and playtested the game prototype during the last semester of their senior year in nursing school. Playtesting is a form of feedback that supports an iterative design process that is critical to game development. A 10-question survey was coupled with group discussions addressing five broad themes of an archetypical digital educational mini game to yield feedback on game design, play, and content. Four rounds of playtesting and incorporating feedback supported the iterative process. Accelerated bachelor of science in nursing student playtester feedback suggests that the digital educational mini game prototype has potential for offering an engaging, playful game experience that will support securing the fundamental principles of arterial blood gases. Next steps are to test the digital educational mini game for teaching and learning effectiveness. (C) 2016 Elsevier Inc. All rights reserved.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/002-463-666-213-787 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Arterial blood gases; Educational digital games; Interdisciplinary collaboration; Mini games; Nursing students; Serious games; arterial blood; blood gas; clinical article; dept.nur; human; learning; nursing education; nursing student; teaching

Enhancing student nurse learning through participation in a community-based educational program for children and families - Krol, Maria; Resha, Cheryl; Glendon, Mary Ann (Journal of Community Health Nursing, 2016)
Health disparities, especially among minorities, persist; obesity is a national concern; and the combined effect can be significant for families and populations. In an effort to address obesity at an early age, the National Association of Hispanic Nurses (NAHN), developed the Muevete USA project. Muevete USA (from the Spanish verb for to move) features five lesson plans on healthy lifestyles for children and their families. This article describes Muevete USA, the partnership with a local school of nursing, the implementation of the program at the local level and the emerging program and student outcomes of a successful partnership.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/051-475-177-637-576 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Child; Child Health; Community-Based Participatory Research; Humans; Obesity; Schools; Students; Nursing; child; child health; dept.nur; human; nursing student; obesity; participatory research; school

Using Schools of Nursing to Help Fill the Gap - Resha, Cheryl (NASN School Nurse, 2016)
The shortage of school nurses, school nurses covering multiple buildings, and the expanded role of the school nurse has called for innovative ideas to meet the growing health care needs of youth. Partnering with local schools of nursing may be a welcomed strategy. This brief article will share the benefits of hosting student nurses as well as identify ways to begin these partnerships. © 2016 The Author(s).
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-767-614-188-699 tex.type: [object Object]
Keywords: Adult; Curriculum; Education; Nursing; Baccalaureate; Female; Humans; Interprofessional Relations; Male; Middle Aged; Organizational Innovation; School Health Services; School Nursing; Schools; Nursing; Students; Nursing; United States; adult; curriculum; dept.nur; education; female; health promotion; human; male; middle aged; nursing education; nursing student; organization; organization and management; partnerships; public relations; school health nursing; school health service; schools of nursing; student nurses

Predictors of types of caregiver burden - Unson, Christine; Flynn, Deborah; Haymes, Elayne; Sancho, Diane; Glendon, Mary Ann (Social Work in Mental Health, 2016)
This study identified the types of caregiver stress and the caregiver and care management characteristics that are associated with this stress. 169 caregivers were recruited from a variety of community settings that cater to caregivers in a New England metropolitan area. They completed the Zarit Burden Interview (ZBI) and a questionnaire concerning their care recipient and caregiving arrangements. Principal Components Analysis on the ZBI resulted in five factors: personal strain/loss, uncertainty/inadequacy, social strain/embarrassment, anger, and dependency. The average age of the caregiver was 59.95 years (SD = 11.75) and the average age of the CR was 83.44 years (SD = 7.88). Of the 169 caregivers, 82% were women, 61.5% daughters/in-law or wives (12.9%), 34.3% were solo caregivers; 16.8% little or no burden, 39.9% reported mild to moderate burden, 35% moderate to severe burden, and 8.4% had severe burden. Dependency (22.4%) and personal strain/loss (13.7%) had the highest proportions reported as “often” to “nearly always.” The ZBI was predicted by only two caregiver characteristics, indicating that it is not sensitive to the experiences of different types of caregivers. Caregivers experience different types of burden depending on their gender, kinship roles, and levels of involvement in the care of their older relative. Solo caregiver status and age (younger) significantly predicted most if not all 5 burden types. Solo and young caregivers experienced the highest levels of caregiver burden. Social work practice must identify the caregiver’s life stage and other and self-expectations in relation to dependency, personal loss, embarrassment, anger, or uncertainty. © 2016 Taylor & Francis.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-743-882-854-036 tex.type: [object Object]
Keywords: Caregiver burden; United States; adult; aged; anger; caregiver burden; controlled study; dependency; dept.nur; dept.pch; expectation; female; gender; human; human experiment; interview; male; principal component analysis; questionnaire; recipient; social work practice; strain; uncertainty

Effectiveness of a role-modeling intervention on student nurse simulation competency - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2013)
Novice nurses are often inadequately prepared to respond to complex, patient care situations where patients' conditions deteriorate. Exposure to a video-taped intervention that role-models and reinforces expected behavior of an expert nurse before participation in a simulation may improve student nurse performance in a cost-effective manner. The primary purpose of this quasi-experimental pre-test, post-test study was to assess the preliminary effectiveness of a theory based role-modeling intervention on enhancing student nurse competency in responding to a simulated response to rescue event. Performance was measured by a previously validated Heart Failure Simulation Competency Evaluation Tool (c) (HFSCET). Total mean scores on the HFSCET for the pre-test (59.08) and post-test (87.08) were significantly different (p = .000); students performed better on the post-test after exposure to the role-modeling intervention. A power analysis indicated a large effect size (effect size = .926; alpha = 0.50; power = 0.991). Students who had a greater number of days between the intervention and the post-test had a lower score. This innovative intervention based on established learning theory may change the way educators prepare novice students to achieve expected clinical competencies in graded simulation performance assessments. (c) 2013 International Nursing Association for Clinical Simulation and Learning. Published by Elsevier Inc. All rights reserved.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-811-864-193-208 tex.type: [object Object]
Keywords: Intervention; Nursing students; Performance assessment; Simulation; dept.nur

Competency assessment in simulated response to rescue events - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2012)
Background: Reliable and valid instruments are needed to assess patient safety competencies, specifically nursing students' ability to appropriately respond to simulated rescue events. Methods: This was an instrument development study conducted with 152 senior nursing students in 2 phases. Results: Student groups performed poorly during the simulation scenario, with mean scores on the Heart Failure Simulation Competency Evaluation Tool ranging from 46% to 56%. Interrater reliability increased to .839 after item revision during Phase 2 of the study. Discussion: This simulation competency assessment package is ready to be tested with more diverse student groups and novice nurses in the practice setting. © 2012 International Nursing Association for Clinical Simulation and Learning.
7 citations (Crossref) [2023-10-31] Citation Key Alias: pop00146 tex.type: [object Object]
Keywords: Failure to rescue; Instrument development; Nursing students; Patient safety; Simulation; dept.nur

Nurse practitioners in home health care: an update - Neal‐Boylan, Leslie; Mager, Diana; Kazer, Meredith Wallace (Home Health Care Management & Practice, 2012)
Nurse practitioners are playing an increasingly visible role in home care. The Institute of Medicine in collaboration with the Robert Wood Johnson Foundation recommends wider use of Advanced Practice Registered Nurses and there has been growing interest in using the role in home care.1 However, the physician remains the provider who must sign home health agency paperwork and orders. The "Home Health Care Planning Improvement Act" would allow nurse practitioners to certify Medicare-sponsored treatment plans.2 This article will discuss the status of the nurse practitioner role in home care, the impact of reimbursement on home care services, how the passage of the new act would change current practice, and a vision for the future role of the nurse practitioner in home health care. © 2012 SAGE Publications.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00276 tex.type: [object Object]
Keywords: Home Health Care Improvement Act; conceptual model; dept.nur; home health care; nurse practitioner; transitional care model

An exploration and comparison of the worklife experiences of registered nurses and physicians with permanent physical and/or sensory disabilities. - Neal-Boylan, Leslie (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2012)
PURPOSE: To examine the worklife experiences of physicians, to further the exploration of the worklife experiences of nurses with disabilities, and to discover how the two healthcare professions compare with each other with regard to these experiences., METHODS: This study employed the research tradition of interpretive naturalistic inquiry and used constant comparative analysis to collect and analyze the data., FINDINGS: Despite the cultural and educational differences between physicians and RNs, their experiences as healthcare professionals with self-identified permanent physical and/or sensory disabilities were very similar. The research team identified five core themes., CONCLUSIONS: Healthcare professionals, including staff and administrators, need to make an effort to retain employees as turnover and predicted shortages are likely to jeopardize the current healthcare system., CLINICAL RELEVANCE: Modifications can be made within both professions to support people with disabilities and to enable them to contribute to their professions using their abilities to think critically, solve problems, and care for patients safely. Copyright © 2012 Association of Rehabilitation Nurses.
17 citations (Crossref) [2023-10-31] Place: United States Neal-Boylan, Leslie. Department of Nursing, Southern Connecticut State University, New Haven, CT, USA. leslie.neal-boylan@yale.edu
Keywords: *Disabled Persons/rh [Rehabilitation]; *Employment; *Nurses; *Physicians; Adult; Aged; Aged; 80 and over; Career Choice; Disability; Disabled Persons; Disclosure; Emotions; Employment; Female; Humans; Male; Middle Aged; Nurse; Nurse workforce; Nurses; Patient Safety; Physician; Physicians; United States; Work life; adult; aged; article; comparative study; decision making; dept.nur; disabled person; emotion; employment; female; human; interpersonal communication; male; middle aged; nurse; patient safety; physician

The career trajectories of health care professionals practicing with permanent disabilities. - Neal-Boylan, Leslie; Hopkins, Amy; Skeete, Rachel; Hartmann, Sarah B; Iezzoni, Lisa I; Nunez-Smith, Marcella (Academic medicine : journal of the Association of American Medical Colleges, 2012)
PURPOSE: The authors sought to generate insights and hypotheses about the professional experiences of registered nurses and physicians with self-identified disabilities to inform local and national policy conversations on supporting a diverse health care workforce., METHOD: In 2009-2010, the authors conducted in-depth interviews in person and over the telephone with a sample of licensed registered nurses and physicians across the country who self-identified as having a permanent disability. They coded the interview transcripts to identify key themes across the participants' responses., RESULTS: The authors interviewed 10 registered nurses and 10 physicians. Five novel and consistent themes emerged from the data analysis: (1) Living and working with a physical/sensory disability narrows the career choices and trajectories of nurses and physicians, (2) nurses and physicians struggle with decisions regarding whether to disclose and discuss their disabilities at work, (3) nurses and physicians rarely seek legally guaranteed workplace accommodations, instead viewing patient safety as a personal responsibility, (4) interpersonal interactions often reflect the institutional climate and set the tone for how welcome nurses and physicians feel at work, and (5) reactions to workplace disability-related challenges run an emotional spectrum from anger and grief to resilience and optimism., CONCLUSIONS: The responses revealed several missed opportunities for supporting health care professionals with disabilities in the workplace. These findings should inform the continuing debate regarding what defines "reasonable accommodation" and how to create a workplace that is welcoming for nurses and physicians with disabilities.
24 citations (Crossref) [2023-10-31] Place: United States Neal-Boylan, Leslie. Department of Nursing, Southern Connecticut State University, New Haven, USA.
Keywords: *Attitude of Health Personnel; *Career Choice; *Disabled Persons/px [Psychology]; *Nurses/px [Psychology]; *Physicians/px [Psychology]; Adult; Aged; Aged; 80 and over; Female; Health Personnel; Humans; Interprofessional Relations; Interviews as Topic; Male; Middle Aged; Truth Disclosure; United States; Workplace/px [Psychology]; dept.nur

Nurses with sensory disabilities: their perceptions and characteristics. - Neal-Boylan, Leslie; Fennie, Kristopher; Baldauf-Wagner, Sara (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2011)
A survey design was used to explore the perceptions and characteristics of registered nurses (RNs) with sensory disabilities and their risk for leaving their jobs. An earlier study found that nurses with disabilities are leaving nursing and that employers do not appear to support these nurses. Work instability and the mismatch between a nurse's perceptions of his or her ability and the demands of their work increase risk for job retention problems. This study's convenience sample of U.S. RNs had hearing, vision, or communication disabilities. Participants completed a demographic form, three U.S. Census questions, and the Nurse-Work Instability Survey. Hospital nurses were three times more likely to be at risk for retention problems. Nurses with hearing disabilities were frustrated at work. Hearing difficulties increased with years spent working as a nurse. Many nurses with sensory disabilities have left nursing. Early intervention may prevent work instability and increase retention, and rehabilitation nurses are ideally positioned to lead early intervention programs.
10 citations (Crossref) [2023-10-31] Place: United States Neal-Boylan, Leslie. Southern Connecticut State University, New Haven, CT, USA. nealboylanL1@southernct.edu
Keywords: *Communication Disorders; *Disabled Persons; *Employment; *Nursing Staff; *Personnel Management; *Sensation Disorders; Adult; Aged; Communication Disorders; Communication Disorders/rh [Rehabilitation]; Disability; Disability Evaluation; Disabled Persons; Disabled Persons/rh [Rehabilitation]; Employment; Hearing Impaired Persons; Humans; Middle Aged; Nursing Staff; Nursing Staff; Hospital; Nursing shortage; Personnel Management; Persons With Hearing Impairments/rh [Rehabilitation]; Rehabilitation Nursing; Sensation Disorders; Sensation Disorders/rh [Rehabilitation]; United States; Visually Impaired Persons; Visually Impaired Persons/rh [Rehabilitation]; Workforces; adult; aged; article; communication disorder; dept.nur; disability; disabled person; employment; human; middle aged; nursing staff; patient; personnel management; rehabilitation nursing; sensory dysfunction

Dementia and Caregiver Stress: An Application of the Reconceptualized Uncertainty in Illness Theory. - Unson, Christine; Flynn, Deborah; Glendon, Mary Ann; Haymes, Elayne; Sancho, Diane (Issues in mental health nursing, 2015)
The Reconceptualized Uncertainty in Illness Theory (RUIT) was used to investigate antecedents to, appraisals of, and ways of coping with stressful caregiving. Four focus groups with caregivers (8 males and 16 females) of relatives with dementia were conducted; 15 cared for their parents and the remainder cared for their spouses. They were recruited from an adult care center and other community settings in a metropolitan area in New England. The discussions were audiotaped and transcribed verbatim. Two researchers independently coded the transcripts. Thematic analysis was structured according to the RUIT. The study is unique in its application to caregivers as opposed to patients and to all of the elements of the RUIT. Caregivers experience uncertainty in similar ways to patients with life-altering illness. Symptom severity–lack of personal boundaries, repetitive and aggressive behaviors, and the need for constant care–was the most frequent source of stress. The appraisals were mostly negative and included feelings of resentment, a lack of support from family members, financial strains, and loss of freedom. Self-improvement and self-care were important aspects of coping. Spirituality and humor were other coping skills that respondents used. Not all respondents said they were coping and some also reported that support from health care providers was not always helpful. Nurses can help improve coping by explaining the factors that contribute to caregiver strain and uncertainty, and by assisting caregivers to anticipate the effects of the caregiving role.
16 citations (Crossref) [2023-10-31] Place: England Unson, Christine. Southern Connecticut State University, Department of Public Health, New Haven, Connecticut, USA.
Keywords: *Adaptation; Psychological; *Caregivers/px [Psychology]; *Dementia/px [Psychology]; *Stress; Psychological/pc [Prevention & Control]; *Uncertainty; Adaptation; Psychological; Adult; Aged; Aged; 80 and over; Caregivers; Dementia; Dementia/th [Therapy]; Female; Humans; Male; Middle Aged; Models; Psychological; Narration; Stress; Psychological; Stress; Psychological/et [Etiology]; Uncertainty; adaptive behavior; adult; aged; caregiver; dementia; dept.nur; dept.pch; etiology; female; human; male; mental stress; middle aged; peer-reviewed; prevention and control; psychological model; psychology; uncertainty; verbal communication; very elderly

Tick-borne illness - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Tracheostomy care - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Trauma informed care - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Varicella - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Uncertainty in transitions of African American caregivers - Unson, Christine; Flynn, Deborah; Chukwurah, Queendalene; Glendon, Maryann; Testut, Tammy (Issues in Mental Health Nursing, 2020)
The purpose of this study was to gain an understanding of the ambiguities and uncertainties experienced by a diverse group of African-American caregivers. The study applied Schlossberg's transition theory (TT) and Mishel’s revised uncertainty theory to narratives of self-identified African-American caregivers who provided care at least 5 h a week. The men (6) and women (8) were mostly unmarried, mostly caring for a parent or grandparent. The caregivers’ average age was 52 (SD = 19; ages ranged from 24 to 82 years); and the care recipients’ average age was 84 (SD = 9). Six care recipients had dementia and the remainder had multiple disease diagnoses. Narratives were obtained by in-depth interviews or focus group discussions. These were audio-recorded, transcribed verbatim professionally and analyzed independently by trained coders. Schlossberg’s TT contextualized whereas Mishel’s RUIT illuminated the characteristics of the transition, its associated uncertainty, and their relationship to the development of caregiver stress. Situational factors such as difficulties with illness symptoms of the care recipient, conflict between previous experience and current expectations and the adjustments to the new caregiving role, burdened younger caregivers more than older caregivers. Self-factors related to lack of knowledge about the illness and feelings of lack of control. Social support was predominantly provided by family members, and its absence resulted in conflict among siblings and caregiver stress. The most common coping strategies include religiosity, expectations of reciprocity, and coming to terms with the uncertainty. Understanding the feelings, perceptions and needs of caregivers in transition is tantamount to providing nursing care.
4 citations (Crossref) [2023-10-31]
Keywords: Adaptation; Psychological; Adult; African American; African Americans; Aged; Aged; 80 and over; Caregivers; Female; Grandparents; Humans; Male; Middle Aged; Narration; Parents; Social Support; Stress; Psychological; Uncertainty; Young Adult; adult; aged; caregiver; child parent relation; coping behavior; dept.nur; dept.pch; female; grandparent; human; male; mental stress; middle aged; peer-reviewed; psychology; social support; uncertainty; verbal communication; very elderly; young adult

Using Kolb’s Experiential Learning to Educate Nursing Students About Providing Culturally and Linguistically Appropriate Care - Krol, Maria; Adimando, Andrea (Nursing Education Perspectives, 2021)
Over the past decade, the Agency for Healthcare Research and Quality and The Joint Commission have identified that communication problems are a root cause of most serious adverse events and that patients with limited English proficiency are more likely than others to suffer physical harm when such errors occur. It is essential to educate nursing students on the challenges of patients with limited English proficiency and empower them with tools, such as the National Culturally and Linguistically Appropriate Services standards, to minimize this phenomenon in their future nursing practice. We describe an educational intervention designed to accomplish this using Kolb’s experiential learning theory as a foundation for implementation.
0 citations (Crossref) [2023-10-31]
Keywords: Humans; Nursing; Problem-Based Learning; Students; article; dept.nur; experiential learning; human; limited English proficiency; nursing student; peer-reviewed; problem based learning; transcultural care

Autistic spectrum disorders - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Mental health - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Suicide - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

School nurse guidelines for: Abrasions - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Allergies - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Bipolar disorders - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Cardiac conditions - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Depression - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Developmental disabilities - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Enuresis - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Fractures - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Human Papillomavirus (HPV) - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Mosquito-borne disease - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Puncture wounds - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: skin and soft tissue infection (Boils, Cellulitis, Lymphangitis, and MRSA) - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

Scope and standards of practice - Resha, Cheryl Ann (School Nursing: A Comprehensive Text, 2019)
Produced in cooperation with the National Association of School Nurses, this text includes comprehensive coverage of the multiple facets of school nursing—from the foundations of practice and the roles and functions of a school nurse through episodic and chronic illness and behavioral issues, to legal issues and leading and managing within school settings. Written and edited by school nurses and pediatric experts, it features real-world-tested, best practices based on evidence and experience. There’s content here that you won’t find in other books, such as health assessments, individualized health plan development, mental health conditions including adolescent depression, contemporary legal issues, and current policy statements essential to school nursing.
Google-Books-ID: VXWmDwAAQBAJ
Keywords: Medical / Nursing / General; dept.nur

Fibromyalgia treatment and management considerations for nurse practitioners - Stournaras, Dana; Petrovic, Kimberly (Journal of the American Association of Nurse Practitioners, 2019)
The purpose of this case study is to examine the role of the nurse practitioner in the management and treatment of a 35-year-old female patient diagnosed with several conditions, including fibromyalgia posttraumatic stress disorder, anxiety, and depression. Fibromyalgia is a chronic, nonprogressive rheumatic condition with cardinal symptoms of widespread pain and fatigue; it affects more than 5 million people in the United States. This case study examines the nurse practitioner's role in managing fibromyalgia. Benzodiazepines and opioids may be prescribed for treatment of symptoms but prove ineffective, thus contributing to dependency issues. Controversy exists over classification of fibromyalgia as a rheumatologic condition versus a mental health disorder. Fibromyalgia frequently is accompanied by anxiety and depression, making this illness difficult to diagnose and treat.
2 citations (Crossref) [2023-10-31] tex.eissn: 2327-6924 tex.unique-id: ISI:000480702800008
Keywords: Adult; Anxiety; Depression; Female; Fibromyalgia; Humans; Nurse Practitioners; Practice Patterns; Nurses'; Stress Disorders; Post-Traumatic; Treatment Outcome; adult; advanced practice nursing; anxiety; benzodiazepines; chronic disease; depression; dept.nur; female; fibromyalgia; hearing loss; human; nurse practitioner; nurse practitioners; nursing practice; opioids; pain; pathophysiology; peer-reviewed; posttraumatic stress disorder; psychology; role; role concept; treatment outcome

International board certified lactation consultants’ practices regarding supplemental feeding methods for breastfed infants - Penny, Frances; Judge, Michelle P.; Brownell, Elizabeth A.; McGrath, Jacqueline M. (Journal of Human Lactation, 2019)
Background: According to the Baby Friendly Hospital Initiative, when supplementary feeding occurs, mothers should be counseled on the use and risks of feeding bottles and teats. To help support this initiative it is important to understand the supplementation practices of Internationally Board Certified Lactation Consultants (IBCLC)®. Research aims: To determine (1) if the location of an IBCLC’s practice has any impact on supplemental feeding methods; (2) the preferred methods of and the main reasons for supplementation; (3) the level of an IBCLC’s confidence with supplemental feeding methods; (4) who is making supplemental feeding decisions; and (5) if there are geographical differences among supplementation choices and reasons for supplementation. Methods: An exploratory, descriptive, cross sectional survey of IBCLCs was conducted to generate data about their use of supplemental feeding methods. The survey was sent via email invitation through the International Board of Lactation Consultant’s Board of Examiners, with a response rate of 11.5% (N = 2,308). Results: There was no standard method of supplementation among participants. Participants indicated that they were confident advising mothers on alternative feeding methods. Only 17.6% (n = 406) of participants reported that the IBCLC was the caregiver who recommended the method of supplementation used. The majority of participants believed the Supplemental Feeding Tube Device SFTD) best preserves the breastfeeding relationship, and this was their preferred method of supplementation. However, the bottle was ranked as the number one method used in the United States, Australia, and Canada. The use of alternative feeding methods may be overwhelming to the mother. Conclusion: Supplementation by alternative feeding methods might help preserve the breastfeeding relationship and help reach the World Health Organization’s goal of increasing exclusive breastfeeding rates. © The Author(s) 2019.
4 citations (Crossref) [2023-10-31] Citation Key Alias: pop00187 tex.type: [object Object]
Keywords: *Breast Feeding/sn [Statistics & Numerical Data]; *Consultants; *Infant Formula/sn [Statistics & Numerical Data]; *Practice Patterns; Nurses'; Adult; Breast Feeding; Certification; Consultants; Cross-Sectional Studies; Female; Global Health; Humans; Infant Formula; Infant; Newborn; International Board Certified Lactation Consultant; Middle Aged; Postnatal Care; Practice Patterns; Nurses'; Pregnancy; Surveys and Questionnaires; Young Adult; adult; artificial feeding; artificial milk; breast feeding; breastfeeding support; certification; consultation; cross-sectional study; dept.nur; female; global health; human; middle aged; newborn; nursing practice; peer-reviewed; postnatal care; pregnancy; questionnaire; supplementation; young adult

Teaching accelerated nursing students’ self‐care: A pilot project - Green, Cheryl (Nursing Open, 2020)
Aim A benchmark of 4 has been determined for the reduction of self-reported stress by nursing students’ status post 5 weeks of holistic educational activities and interventions provided by a nurse educator. Design Provision 5 in the American Nurses Association Code of Ethics for Nurses with Interpretive Statements emphasizes the duty of the nurse to not only promote the health and safety of others, but to self as well (ANA, 2015, Code of ethics with interpretive statements, Nursebooks.org). A self-care for nurses’ pilot project was trialled with 25 accelerated nursing students over the course of 5 weeks. Holistic education programmes were facilitated by a nurse educator uninvolved in providing clinical or classroom education to the students. Methods The Standards for Quality Improvement Reporting Excellence (SQUIRE) guidelines are used in this pilot project as a framework to explore standardization of education of nursing students about self-care in nursing programmes and to promote positive health behaviours and student nurses’ insight into how nurses’ self-care can have an impact on patient outcomes. The self-care pilot project introduced the importance of self-care for the pre-licensure nursing student by teaching healthy eating, physical exercise, the value of sleep, use of positive affirmations and aromatherapy to a cohort of accelerated nursing students over the course of 5 weeks. The Star Model of Knowledge Transformation was the theoretical framework for the pilot study. Two questionnaires were used by the principal investigator to obtain participant data, the Project Participant Questionnaire and the Final-Year Group Questionnaire. Results On completion of the self-care for nurses’ pilot, the nursing students reported a reduction in stress and an increased ability to cope with stress after exposure to different holistic stress reduction strategies. An average benchmark of 4.36 was achieved indicating that the nursing students’ self-care had improved status post the interactive teaching intervention. Self-care taught to pre-licensure nursing students by nurse educators can enhance their self-awareness of the importance of stress reduction and care of themselves while enduring the academic rigour and simultaneous clinical practicum experiences in nursing programmes. Applying self-care behaviours to reduction of stress for nursing students may be of benefit to of students as they transition from the pre-licensure to graduate nurse roles. Hence, teaching health behaviours that are self-protective and contribute to maintaining safe clinical environments for nurses and the patients in their care.
10 citations (Crossref) [2023-10-31] tex.ids: greenTeachingAcceleratedNursing2019, lens.org/169-203-251-554-761
Keywords: dept.nur; nurse educators; nursing students; peer-reviewed; self-care; stress reduction

Workplace incivility: Nurse leaders as change agents - Green, Cheryl Ann (Nursing Management, 2019)
An abstract is unavailable.
7 citations (Crossref) [2023-10-31]
Keywords: Humans; Interprofessional Relations; Leadership; Nursing Staff; Organizational Innovation; Workplace; dept.nur; human; leadership; nursing staff; organization; peer-reviewed; public relations; workplace

Bereavement care to minimize bereaved parents' suffering in their lifelong journey towards healing - Denhup, Christine (Applied Nursing Research, 2019)
This article presents select findings from an interpretive phenomenological study which aimed to describe the lived experience of parental bereavement. Six parents, each of whom experienced the death of a child due to cancer at least one year prior, participated in conversational interviews to share what it has been like for them since their child's death. Heideggerian (1962) phenomenology provided the philosophical underpinnings of the study, while van Manen's (1997) phenomenological method guided data collection and analysis. From this methodological approach, a structure of the meaning of parental bereavement experience was revealed. Profound suffering emerged as one essential theme. Pertinent findings related to this theme are discussed. Parents share ways others might minimize their suffering and provide support in their lifelong journey towards healing. Findings will enhance nurses' practice of providing bereavement care, which is an expectation of quality palliative care. Copyright © 2019 Elsevier Inc. All rights reserved.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/134-579-857-152-025 tex.type: [object Object]
Keywords: *Adaptation; Psychological; *Bereavement; *Neoplasms/mo [Mortality]; *Nurse's Role/px [Psychology]; *Nursing Staff; Hospital/px [Psychology]; *Parents/px [Psychology]; *Stress; Psychological/px [Psychology]; Adaptation; Psychological; Adult; Attitude to Death; Bereavement; Child death; Female; Humans; Male; Middle Aged; Neoplasms; Nurse's Role; Nursing Staff; Hospital; Palliative care; Parental bereavement; Parents; Stress; Psychological; Suffering; adult; attitude to death; bereavement; child parent relation; coping behavior; dept.nur; female; human; male; mental stress; middle aged; mortality; neoplasm; nurse attitude; nursing staff; peer-reviewed; psychology

Orientation Learning Needs of Adjunct Clinical Faculty in the United States - Sousa, Monica P.; Resha, Cheryl A. (Nursing Education Perspectives, 2019)
Aim: The aim of the study was to examine the orientation learning needs of adjunct clinical faculty as they transition from expert clinicians to novice educators. Background: Schools of nursing are increasingly using adjunct clinical faculty because of the nurse faculty shortage. Retention is a concern. Method: This descriptive quantitative study used the Needs Assessment Survey for Topic Inclusion in a Guide to Orientation. Adjunct clinical faculty rated the level of importance of orientation topics and if they received needed information. Results: The majority of topics were found to be rated very important or important. Several items deemed very important or important were either not discussed or not sufficiently discussed in orientation. Conclusion: The information obtained demonstrates the vast amount of information that adjunct clinical faculty want and need in an orientation. © 2019 Lippincott Williams & Wilkins.
2 citations (Crossref) [2023-10-31]
Keywords: Adjunct Clinical Faculty; Clinical Nurse Faculty; Clinical Teaching; Faculty Orientation; Faculty; Nursing; Humans; Needs Assessment; Nurses; Transition Into Academia; United States; article; clinical education; clinician; dept.nur; human; learning; needs assessment; nurse; nursing education; peer-reviewed; quantitative analysis

Preventing and alleviating compassion fatigue through self-care: An educational workshop for nurses - Adimando, Andrea (Journal of Holistic Nursing, 2018)
Though various authors have refined and described the concept of compassion fatigue (CF), the overarching features, predisposing factors, and potential consequences remain relatively consistent. Available literature demonstrates that caregivers caring for patients who are chronically ill and/or traumatized are at highest risk for developing CF. Potential consequences for unmitigated CF include physical, emotional, and work-related consequences, all of which can have negative effects on the quality and safety of care and degree of engagement with one’s employer. CF is further exacerbated by exposure to cumulative, unresolved stress and neglect of one’s own emotional needs over time. Caregivers must be knowledgeable on CF’s risk factors, symptoms, and management strategies to decrease its incidence and negative impacts. This article details the creation, execution, and evaluation of an evidence-based practice change project implemented with the goal of increasing knowledge needed to prevent, identify, and alleviate CF in high-risk nurses. The project involved a series of educational workshops containing information on CF’s risk factors, symptoms, and consequences, with a strong emphasis on self-awareness, self-care, and stress management. Pre- and postknowledge tests showed a significant increase in knowledge was achieved via the workshops, and qualitative surveys indicated a high level of participant satisfaction with the program contents, format, and impact.
21 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-914-713-725-562, pop00211 tex.type: [object Object]
Keywords: Adult; Burnout; Professional; Compassion Fatigue; Female; Holistic Nursing; Humans; Inservice Training; Male; Middle Aged; Nurses; Quality of Life; Self Care; Surveys and Questionnaires; adult; burnout; caring; compassion fatigue; dept.nur; educators; female; grief/loss/suffering; health and wellness coaching; holistic nursing; human; in service training; male; meditation/mindfulness; middle aged; nurse; nurses; peer-reviewed; prevention and control; psychology; quality of life; questionnaire; self care; stress and coping; stress management/relaxation; trauma/posttrauma

Peaches and crocs: A story of gratitude for nurses - Resha, Cheryl Ann (American Nurse Today: Insights, 2018)
My story began when I was 49 years young and told I had Stage IV colorectal cancer. That was almost 12 years ago, and today I am one of the fortunate ones—not only has it been almost 12 more years of living, but my oncologist has used the word “cured”. Like most cancer patients and …
Keywords: dept.nur; ⛔ No DOI found

Cup Feeding as a Supplemental, Alternative Feeding Method for Preterm Breastfed Infants: An Integrative Review. - Penny, Frances; Judge, Michelle; Brownell, Elizabeth; McGrath, Jacqueline M (Maternal and child health journal, 2018)
Background The benefits of human milk for the preterm infant are well established. Preterm infants have lower breastfeeding rates and often face breastfeeding challenges. It is important that feeding practices for preterm infants optimize their chances of breastfeeding. Objective The purpose of this integrated review is to synthesize and critically analyze research related to the safety and efficacy of cup feeding as an alternative, supplemental feeding method for breastfed infants. Data Sources The electronic data bases of PubMed, CINAHL and were used to identify studies published in English from 1998- 2017. Design Using inclusion and exclusion criteria, 27 articles were initially assessed. After further screening 19 articles were included in the full review and of these 5 more were excluded. Lastly, an in-depth review of these 14 studies resulted in 2 more exclusions, for a total of 12 studies that met full inclusion and exclusion criteria. Review Methods Studies were examined for information on safety and efficacy of cup feeding as an alternative, supplemental feeding method for preterm breastfed infants. Studies were grouped into categories of outcomes that included (a) safety and physiologic properties; (b) breastfeeding outcomes. Results Use of cup feeding resulted in more stable heart rate and oxygen saturation than bottle feeding with similar weight gain. Additionally, breastfeeding rates were higher at discharge with continued higher rates at 3 and 6 months post-discharge for cup fed infants. Conclusions Premature infants face more breastfeeding obstacles than term infants. The potential for cup feeding as an alternative to bottle-feeding for breast fed preterm infants is positively supported by these results It is fundamentally important for NICU professionals to establish a protocol, education and training for the potential use of this feeding method for this vulnerable population.
13 citations (Crossref) [2023-10-31] Place: United States Penny, Frances. Department of Nursing, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Pennyf1@southernct.edu. Penny, Frances. School of Nursing, University of Connecticut, Storrs, CT, USA. Pennyf1@southernct.edu. Judge, Michelle. School of Nursing, University of Connecticut, Storrs, CT, USA. Brownell, Elizabeth. Connecticut Children's Medical Center, Hartford, CT, USA. Brownell, Elizabeth. School of Medicine, University of Connecticut, Farmington, CT, USA. McGrath, Jacqueline M. School of Nursing, University of Connecticut, Storrs, CT, USA. McGrath, Jacqueline M. Connecticut Children's Medical Center, Hartford, CT, USA.
Keywords: *Bottle Feeding; *Breast Feeding/mt [Methods]; *Cooking and Eating Utensils; *Enteral Nutrition/mt [Methods]; *Feeding Methods; *Infant; Premature/ph [Physiology]; Alternative feeding; Bottle Feeding; Breast Feeding; Breastfeeding; Cooking and Eating Utensils; Cup feeding; Enteral Nutrition; Enteral Nutrition/is [Instrumentation]; Feeding Methods; Female; Humans; Infant; Newborn; Infant; Premature; Infants; Male; Preterm; bottle feeding; breast feeding; dept.nur; devices; enteric feeding; female; food intake; human; kitchen; male; newborn; peer-reviewed; physiology; prematurity; procedures

Incivility among nursing professionals in clinical and academic environments: emerging research and opportunities - Green, Cheryl (IGI Global, 2018)
Traditionally, nursing is acknowledged as a caring profession and is associated with advocating for others. However, incivility is increasingly occurring amongst nurses, both in the clinical and academic environments, and is causing affected nurses both psychological and physical harm. Incivility Among Nursing Professionals in Clinical and Academic Environments: Emerging Research and Opportunities provides emerging views and consequences surrounding workplace bullying in the healthcare profession including recognizing the signs and symptoms of incivility in the workplace, identifying ways in which affected nurses can seek help, and examining healthy methods of coping with the incivility. Featuring coverage on a broad range of topics such as human resources, therapy, and clinical nursing, this book is ideally designed for nurses, managers, healthcare workers and consumers, hospital and clinical staff, researchers, students, and policymakers.
Citation Key Alias: greenIncivilityNursingProfessionals2019, lens.org/024-055-981-898-128, pop00327
Keywords: dept.nur

Using case study methodology to explore the role of discrimination in workplace incivility - Green, Cheryl (Journal of National Black Nurses' Association: JNBNA, 2018)
Exclusionary behaviors can be detrimental to the health and well-being of faculty in the workplace. When colleagues are judged by their peers because of the color of their skin, the language they speak, their gender, or who they choose to love (lesbian, gay, bisexual, transgender, asexual, or questioning), affected faculty are left emotionally and physically vulnerable. Institutions of higher learning must set standards of zero tolerance for faculty-to-faculty incivility. With standards taken from each faculty discipline, codes of conduct can be implemented not only at a departmental level, but also throughout the educational system.
Keywords: Discrimination; Exclusionary; Faculty; Humans; Incivility; Interprofessional Relations; Prejudice; dept.nur; peer-reviewed

Complimentary Care: When Our Patients Request to Pray. - Green, Cheryl Ann (Journal of Religion and Health, 2018)
Prayer is viewed in modern medicine as a complimentary alternative treatment. However, to many patients, it is a source of hope and comfort. Patients, when facing illness, advanced disease, disability or death, can benefit from prayer. For healthcare providers, comfort with praying with patients can be deemed as unprofessional conduct or blurred therapeutic boundaries, particularly, when prayer is offered to patients' unsolicited by the patient or their family member(s). Therefore, it is imperative that healthcare providers await the request of prayer by the patient before prayer is initiated.
5 citations (Crossref) [2023-10-31] Place: United States Green, Cheryl Ann. Southern Connecticut State University, 501 Crescent Street, Jennings Hall, Office 121, New Haven, CT, 06515, USA. Greenc16@southernct.edu.
Keywords: *Attitude of Health Personnel; *Delivery of Health Care; *Faith Healing; *Pastoral Care/mt [Methods]; *Religion; *Spirituality; Attitude of Health Personnel; Delivery of Health Care; Faith Healing; Family; Healthcare providers; Humans; Nurse's Role; Nurses; Pastoral Care; Patients; Prayer; Religion; Religion and Medicine; Spirituality; dept.nur; family; health care delivery; health personnel attitude; human; nurse attitude; pastoral care; peer-reviewed; procedures; religion; spiritual healing

Contemporary issues: The pre-licensure nursing student and medication errors. - Green, Cheryl (Nurse Education Today, 2018)
In Modern health care, the creation of cultures of safety for patients is of the upmost importance. Impacting the institutional stabilization of health care facilities safety initiatives, is the preparation of pre-licensure nursing students to safely administer medications to patients. Therefore, preparation of the pre-licensure nursing student must be evidence-based practice focused and incorporate innovative ways to reduce the potential for medication errors. Copyright © 2018. Published by Elsevier Ltd.
8 citations (Crossref) [2023-10-31] Place: Scotland Green, Cheryl. Southern Connecticut State University, Department of Nursing, Jennings Hall Office 121, United States. Electronic address: Greenc16@southernct.edu.
Keywords: *Clinical Competence; *Medication Errors/nu [Nursing]; *Students; Nursing; Clinical Competence; Education; Nursing; Baccalaureate; Humans; Licensure; Nursing; Medication Errors; Medication Errors/pc [Prevention & Control]; Medication errors; Pre-licensure nursing students; Prevention; Students; Nursing; adult; clinical competence; dept.nur; drug safety; editorial; evidence based practice center; health care facility; human; licensing; medication error; nursing; nursing education; nursing student; peer-reviewed; prevention and control

Using instrumentation in psychiatric nursing to assess documentation of the nursing process for emergent non-psychiatric patient events. - Green, Cheryl (Archives of Psychiatric Nursing, 2018)
Ongoing education of experienced psychiatric nurses is imperative given the historically complex health presentations of psychiatric patients. Psychiatric patients tend to have medical co-morbidities and often do not have the financial resources for preventative health care. The hospitalization for acute psychiatric stabilization, is an opportunity for psychiatric nurses to teach and advocate for patients' physiological and psychological health. Documentation of patients' changes in condition and overall clinical presentation, is necessary to ensure patients' health care needs are met. Copyright © 2018 Elsevier Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] Place: United States Green, Cheryl. Southern Connecticut State University, Department of Nursing, Jennings Hall, Office 121, New Haven, CT 06515, United States; Yale-New Haven Psychiatric Hospital, New Haven, CT 06510, United States. Electronic address: Greenc16@southernct.edu.
Keywords: *Documentation/st [Standards]; *Inservice Training/mt [Methods]; *Nursing Process; *Psychiatric Nursing; Documentation; Educational Measurement; Educational Measurement/sn [Statistics & Numerical Data]; Hospitalization; Humans; Inservice Training; Nurses; Nursing Process; Nursing process; Patients; Psychiatric Nursing; Psychiatry; Surveys and Questionnaires; adult; article; comorbidity; dept.nur; documentation; education; health care need; hospitalization; human; in service training; mental patient; nurse; nursing process; peer-reviewed; procedures; psychiatric nursing; psychological well-being; questionnaire; standards; statistics and numerical data

New nursing faculty and incivility: applying mindfulness-based strategies - Green, Cheryl (Holistic Nursing Practice, 2018)
Workplace incivility remains a problem within the nursing profession. As nurse leaders, we must recognize and not ignore the complexity of cultures that have adapted incivility into the work environment. Nursing education is a discipline that requires collaborative team work, independent drive, and commitment. New nursing faculty experiencing incivility can use mindfulness-based meditation approaches to cope with uncivil behaviors experienced within the workplace. Nurse educators applying the concepts of mindfulness can learn how to provide themselves self-care by reducing stress, as enhanced daily awareness of peace and calm are incorporated into their lifestyle. Mindfulness provides a realization that control can only be given to other persons when an individual allows or accepts another's negative behaviors. Awareness of the value and importance of oneself can assist the nurse educator experiencing incivility to maintain his or her emotional, physical, and spiritual health despite the volatility of the work environment.
9 citations (Crossref) [2023-10-31] tex.eissn: 1550-5138 tex.unique-id: ISI:000417936200002
Keywords: Attitude of Health Personnel; Bullying; Faculty; Nursing; Humans; Incivility; Interprofessional Relations; Mindfulness; Stress; Psychological; Universities; Workplace; academia; adult; awareness; bullying; complication; dept.nur; etiology; female; health personnel attitude; human; human experiment; incivility; leadership; lifestyle; male; meditation; mental stress; mindfulness; nursing education; nursing faculty; occupation; organization and management; peer-reviewed; psychology; public relations; self care; standards; stress; teamwork; trends; university; work environment; workplace

What is the evidence for use of a supplemental feeding tube device as an alternative supplemental feeding method for breastfed infants? - Penny, Frances; Judge, Michelle; Brownell, Elizabeth; McGrath, Jacqueline M. (Advances in Neonatal Care, 2018)
Background: According to the Healthy People 2020 goals, the sustainability of breastfeeding duration rates within the United States has not been achieved. To increase these rates, it is important that women with breastfeeding difficulties receive the support needed to continue breastfeeding. When supplementation occurs, it is essential that the breastfeeding relationship be preserved. Various methods of supplementation are often recommended including use of the supplemental feeding tube device (SFTD). Purpose: The question guiding this brief is “What evidence exists to support the use of an SFTD as a method of supplementation for breastfed infants?” Search Strategy: The PubMed and CINAHL databases were queried for original research published in English from 1990 through July 2016. Search terms included “supplemental feeding tube,” “breastfeeding,” “term infants,” “premature infants,” “Supplemental Nursing System,” “Lact-aid,” and “supply line.” Findings: Very limited research exists on the use of SFTDs as a method of supplementation for breastfed infants; however, existing research suggests that an SFTD may be useful as a supplementation method for breastfed infants. High-quality research is needed to evaluate the efficacy of using an SFTD for supporting exclusive and all breastfeeding rates. Implications for Practice: Nurses and providers need to be educated and trained in the use of SFTDs as well as all supplemental feeding methods. Information on efficacy and SFTD use should also be included in policies related to breastfeeding and human milk use. Implications for Research: Further research should determine best methods of supplementation for breastfed infants and should examine differences in breastfeeding rates when using the SFTD for supplementation.
10 citations (Crossref) [2023-10-31] tex.eissn: 1536-0911 tex.unique-id: ISI:000426548300007
Keywords: Breast Feeding; Breastfeeding; Dietary Supplements; Enteral Nutrition; Humans; Infant; Newborn; Nursing Care; Treatment Outcome; breast feeding; breastfeeding support; breastmilk; dept.nur; dietary supplement; enteric feeding; human; human milk; newborn; newborn intensive care; nursing care; peer-reviewed; preterm infant; procedures; supplemental feeding; supplemental feeding device; treatment outcome

Evaluation of the McMahon Competence Assessment Instrument for use with midwifery students during a simulated shoulder dystocia - McMahon, Erin; Jevitt, Cecilia; Aronson, Barbara (Journal of Midwifery & Women's Health, 2018)
IntroductionIntrapartum emergencies occur infrequently but require a prompt and competent response from the midwife to prevent morbidity and mortality of the woman, fetus, and newborn. Simulation provides the opportunity for student midwives to develop competence in a safe environment. The purpose of this study was to determine the inter-rater reliability of the McMahon Competence Assessment Instrument (MCAI) for use with student midwives during a simulated shoulder dystocia scenario. MethodsA pilot study using a nonprobability convenience sample was used to evaluate the MCAI. Content validity indices were calculated for the individual items and the overall instrument using data from a panel of expert reviewers. Fourteen student midwives consented to be video recorded while participating in a simulated shoulder dystocia scenario. Three faculty raters used the MCAI to evaluate the student performance. These quantitative data were used to determine the inter-rater reliability of the MCAI. ResultsThe intraclass correlation coefficient (ICC) was used to assess the inter-rater reliability of MCAI scores between 2 or more raters. The ICC was 0.86 (95% confidence interval, 0.60-0.96). Fleiss's kappa was calculated to determine the inter-rater reliability for individual items. Twenty-three of the 42 items corresponded to excellent strength of agreement. DiscussionThis study demonstrates a method to determine the inter-rater reliability of a competence assessment instrument to be used with student midwives. Data produced by this study were used to revise and improve the instrument. Additional research will further document the inter-rater reliability and can be used to determine changes in student competence. Valid and reliable methods of assessment will encourage the use of simulation to efficiently develop the competence of student midwives.
1 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000428796300010 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Article; Clinical Competence; Dystocia; Education; Nursing; Educational Measurement; Female; Humans; Infant; Newborn; McMahon Competence Assessment Instrument; Midwifery; Nurse Midwives; Observer Variation; Pilot Projects; Pregnancy; Reproducibility of Results; Shoulder; Simulation Training; Video Recording; assessment; clinical competence; competence; content validity; controlled study; correlation coefficient; dept.nur; dystocia; education; evaluation; expert system; female; human; instrument; intrarater reliability; midwife; midwifery education; midwifery student; newborn; nurse midwife; nursing education; observer variation; obstetric procedure; peer-reviewed; pilot study; pregnancy; priority journal; procedures; quantitative analysis; quantitative study; reliability; reproducibility; scoring system; shoulder; shoulder dystocia; simulation; simulation training; standards; teacher; validation study; validity; videorecording

The elderly and the opioid epidemic: A case study - Green, Cheryl A. (Addictive Disorders & Their Treatment, 2017)
Opioid addiction is a problem within the United States that is impacting all age groups. The elderly are a population that is seldom discussed as being affected by opioids. Physiologically, the older adult is more susceptible for complications associated with an alteration in pharmacokinetics and late diagnosis of diseases such as viral hepatitis C. Health promotion for this population is imperative in the prevention and treatment of opioid addiction problems.
1 citations (Crossref) [2023-10-31]
Keywords: Article; Hepatitis C virus; United States; aged; boceprevir; buprenorphine plus naloxone; case report; clinical article; creatinine; creatinine blood level; dept.nur; diamorphine; follow up; health care personnel; health promotion; hepatitis C; human; male; medicare; methadone; methadone treatment; older adults; opiate addiction; opioids; oxycodone; priority journal; protein blood level; self report; telaprevir; urea nitrogen blood level; weight reduction

Examining school-aged youth - Adimando, Andrea (Legal Resources for School Health Services, 2017)
A comprehensive resource that addresses the legal issues regarding school health services for school nurses, school administrators and school attorneys. Over 50 topics are included including information on federal laws, compliance, medication administration, professional licensure and malpractice, minor rights and mental health and much more. Over 70 authors include school nurse experts, and education and nurse attorneys. Each chapter is evidence based and peer reviewed by both school nurse content experts and attorneys. Responds to questions submitted by school nurses and school administrators. A reference that will support school nurse and school health practice, enhance care to children and provide guidance to protect the school and school nurse.
Keywords: dept.nur

The process for delegation in the school setting - Resha, Cheryl Ann (Legal Resources for School Health Services, 2017)
A comprehensive resource that addresses the legal issues regarding school health services for school nurses, school administrators and school attorneys. Over 50 topics are included including information on federal laws, compliance, medication administration, professional licensure and malpractice, minor rights and mental health and much more. Over 70 authors include school nurse experts, and education and nurse attorneys. Each chapter is evidence based and peer reviewed by both school nurse content experts and attorneys. Responds to questions submitted by school nurses and school administrators. A reference that will support school nurse and school health practice, enhance care to children and provide guidance to protect the school and school nurse.
Keywords: dept.nur

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education–accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
10 citations (Crossref) [2023-10-31] Citation Key Alias: roneyTechnologyUseTechnological2017a
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education; Nursing; Baccalaureate; Educational Status; Educational Technology – Utilization; Faculty Development; Faculty Practice; Faculty; Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools; Nursing; Self-Efficacy; Socioeconomic Factors; Students; Nursing; Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching

Nursing students' access to test banks: are your tests secure? - Madara, Bernadette; Resha, Cheryl; Krol, Maria D.; Lacey, Kimberly; Martin, Elaine F.; O'Sullivan, Cynthia; Smith, Jan Weingrad (Journal of Nursing Education, 2017)
Background: Schools of nursing have moved to multiple choice test questions to help prepare students for licensure and practice. However, students can buy test banks to help them “get through” nursing school. Accurate assessment of nursing students' knowledge and judgment comprises access to test banks. Method: The purpose of this exploratory study was to gain an understanding about nursing faculty's knowledge concerning test bank security issues, to assess whether publishers were aware of this issue, and vendor's reasons for supplying test banks to students. Results: Overall, the results indicated that the majority of faculty were unaware of student access to test banks, and although most do not use test banks verbatim, general consensus existed that test bank security is a concern. Conclusion: Implications include increasing faculty awareness of test bank access by students, supporting educators to develop their own test bank items, and promoting security of all examinations.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000402479200008 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Attitude of Health Personnel; Commerce; Databases as Topic; Education; Nursing; Educational Measurement; Faculty; Nursing; Humans; Internet; Surveys and Questionnaires; awareness; commercial phenomena; consensus; data base; dept.nur; education; exploratory research; health personnel attitude; human; human experiment; nursing; nursing education; questionnaire; student; university

Epidemiology in community health care - Jung, Betty C. (Community & Public Health Nursing: Promoting the Public's Health, 2017)
Help your students understand that community/public health nursing skills benefit their nursing practice as well as patient outcomes in acute care This student-friendly, highly visual text expands students’ viewpoints from the client-nurse relationship to a population focus. Acknowledging that population-focused tools and interventions are needed in acute care, as infection rates continue to rise and nurse-sensitive outcome indictors are closely monitored, Cherie Rector weaves in meaningful, real-life examples, case studies, and perspectives to help students understand that transitions in care are critical in today’s healthcare system. Covering a multitude of community and public settings, situations, and populations, the book helps students learn about promoting health, preventing disease (not just treating it), and protecting at-risk populations—including the elderly, the LGBT community, and veterans. This fully updated 9th Edition encourages students to think more globally and covers new innovations and emerging threats to the public’s health.KEY FEATURESNEW! QSEN sections tie key chapter concepts to quality and safety competencies, such as patient-centered care, teamwork & collaboration, evidence-based practice, quality improvement, and informatics, to help students understand the importance of these concepts.NEW! Application to Population Health explores chapter concepts from a population-focused viewpoint and offers current examples of effective population interventions.What Do YOU Think? encourages students to reflect on thought-provoking current topics or dilemmas, enhancing critical thinking skills.Evidence-based Practice demonstrates how current research examples can be applied to public/community health nursing practice to achieve optimal outcomes.From the Case Files presents case study scenarios with application-based questions, challenging students to reflect on assessment and intervention.Perspectives from nursing students, novice to expert public health nurses, faculty members, policy makers, and clients cover commonly held misconceptions about community health nursing and link between skills across settings.Healthy People 2020 highlights pertinent goals and objectives to promote health.Activities to Promote Critical Thinking at the end of each chapter challenge students, promote critical-thinking skills, and encourage active involvement in solving community health problems.Unique Levels of Prevention Pyramid boxes address a chapter topic and describe nursing actions at each of the three levels of prevention to help students understand this basic community health nursing concept. Content from the text is embedded into two integrated digital learning solutions— Lippincott CoursePoint for pre-licensure programs and Lippincott RN to BSN Online for post-licensure programs—that feature experiential, case-based instructional design aligned with the approach of the Ninth Edition. To learn more about Lippincott CoursePoint and Lippincott RN to BSN Online and to see our Video Cases, please visit http://nursingeducationsuccess.com.
Keywords: dept.nur

A new state of being: the lived experience of parental bereavement - Denhup, Christine Yvonne (OMEGA - Journal of Death and Dying, 2017)
In spite of growing bereavement literature, the meaning of the lived experience of parental bereavement is not well understood. This article presents selected findings from a Heideggerian hermeneutic phenomenological study which aimed to describe the lived experience of bereaved parents who experienced the death of a child due to cancer. Conversational interviews were conducted with six parents who experienced the death of a young child due to cancer at least one year prior to participation. The nature of parental bereavement was revealed to be a new state of being into which parents enter immediately after the death of a child and which has no end point. Findings will equip health professionals and others who work with bereaved parents with a deeper understanding of the meaning of parental bereavement.
15 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000391796100004 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Adult; Bereavement; Child; Child; Preschool; Death; Female; Humans; Male; Models; Psychological; Neoplasms; Parents; Pediatric Nursing; adult; bereavement; child; child death; death; dept.nur; female; hermeneutic phenomenology; human; male; neoplasm; parent; parental bereavement; pediatric nursing; preschool child; psychological model; psychology

Town & gown: Building successful university-community partnerships - King, Beth M.; Gordon, Shirley C.; Barry, Charlotte D.; Goodman, Rhonda; Jannone, Laura T.; Foley, Marie; Resha, Cheryl; Hendershot, Candace (NASN School Nurse, 2017)
1 citations (Crossref) [2023-10-31]
Keywords: dept.nur

School nurse guidelines for: Developmental disabilities - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Enuresis - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Fifth disease (erythema infectiosum) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Homelessness - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Human Papillomavirus (HPV) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Life Threatening cardiac conditions, (Long QT intervals and hypertrophic cardiomyopathy) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Mental health - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Service animals - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Suicide - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Teen pregnancy - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

After the gap analysis: Education and practice changes to prepare nurses of the future - Beauvais, Audrey Marie; Kazer, Meredith Wallace; Aronson, Barbara; Conlon, Suzanne E.; Forte, Pamela; Fries, Kathleen S.; Hahn, Judith M.; Hullstrung, Russell; Levvis, Meg; McCauley, Paula; Morgan, Patricia Padula; Perfetto, Linda; et al. (Nursing Education Perspectives, 2017)
AIM The purpose of the study was to describe the Connecticut Nursing Collaborative-Action Coalition’s work in identifying and addressing gaps between nursing education and practice based on the Institute of Medicine’s Future of Nursing report. BACKGROUND Massachusetts Nurse of the Future (NOF) Competencies highlight the knowledge, skills, and attitudes/behaviors required for professional nurses. Integrating these concepts into the educational system will prepare the nursing workforce to respond to current/future health care needs and population health issues. METHOD Education and practice partners in four regions conducted a gap analysis of the education to practice transition for new graduate nurses using NOF as a framework for assessment. RESULTS Gaps in competencies were similar across regions. However, each organization uniquely addressed curricular gaps to best prepare nurses of the future. CONCLUSION Curriculum improvements will provide students the advantage of being prepared for the rapid changes happening in health care. Copyright © 2017 National League for Nursing
4 citations (Crossref) [2023-10-31]
Keywords: Academic-Practice Partnership; Connecticut; Curriculum; Education; Nursing; Forecasting; Future of Nursing Competencies; Gap Analysis; Humans; Massachusetts; New Graduate Nurses; Nursing Curriculum; Nursing Education; Nursing Staff; article; curriculum; dept.nur; forecasting; health care need; human; human experiment; nursing education; nursing staff; peer-reviewed; population health; skill; student; workforce

School nurse guidelines for: Abdomen-blunt injury - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Abdominal pain / appendicitis - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Abrasions - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Bed bugs - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Bipolar disorder - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Child abuse - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Cytomegalovirus (CMV) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur